Composition for forming adhesive layer, laminate, method for producing laminate, and method for treating laminate
By using an adhesion layer composition containing an unsaturated group-containing alkali soluble resin and an epoxy compound, the problem of reducing the adhesion force during the alkali peeling process is solved, and high alkali resistance and laser processability are achieved, ensuring stable transport of the substrate.
Patent Information
- Application Number
- CN202411202075.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-07-25
- Filing Date
- 2024-08-29
- Publication Date
- 2025-02-28
AI Technical Summary
In the prior art, when using an alkali release liquid to remove the resist layer, the adhesion force of the agent layer is reduced, resulting in insufficient substrate transport stability, and the adhesion layer lacks high alkali resistance and laser processability.
The composition for forming a cross-linking composition consisting of an unsaturated group-containing alkali-soluble resin and an epoxy compound having two or more epoxy groups is used to form a solid cross-linking structure by heat cross-linking, thereby improving alkali resistance, and deteriorating the resin by laser irradiation to peel off the adherend.
High alkali resistance and laser processability of the adsorbent layer are achieved, ensuring the transport stability of the substrate, and improving the removal efficiency of the resist layer.
Smart Images

Figure BDA0005018083190000051 
Figure BDA0005018083190000061 
Figure BDA0005018083190000062
Abstract
Description
Technical Field
[0001] The present invention relates to an adhesive layer-forming composition, a laminate, and a method for producing and treating the laminate. Background Art
[0002] In recent years, as digital devices and the like have become more advanced in functionality, the flexible displays and semiconductor chips mounted thereon have become thinner. However, the flexible displays and semiconductor chips, which have reduced strength due to thinning, are difficult to transport using conventional automatic transport methods.
[0003] Therefore, a method for easily transporting thinned flexible displays, semiconductor chips, etc. is being studied. For example, the following method is used: for a laminate having an adherend such as a semiconductor wafer fixed via an adhesive layer on a support such as a glass substrate, light is irradiated toward the adhesive layer from the support side to deteriorate or decompose the adhesive layer to reduce the adhesive strength, thereby separating the support from the adherend.
[0004] In addition, Patent Document 1 describes a method in which, in a laminate having a support, a supported substrate, an adhesive layer disposed on a surface of the supported substrate on a side supported by the support, and a separation layer disposed between the support and the supported substrate, the separation layer is irradiated with light to deteriorate a polymer contained in the separation layer, thereby separating the support from the supported substrate. According to Patent Document 1, it is believed that the separation layer deteriorates and loses adhesiveness due to being irradiated with light, so that the support and the supported substrate can be easily separated.
[0005] [Prior art literature]
[0006] [Patent Document]
[0007] [Patent Document 1] Japanese Patent Application Publication No. 2012-106486 Summary of the invention
[0008] [Problems to be solved by the invention]
[0009] When forming a pattern of a metal film or the like on a substrate such as a semiconductor wafer, a pattern processing technique using a resist material is generally used.
[0010] For example, when an etching process is used, a pattern of a metal film or the like is sometimes processed on a substrate through the following steps: a) a preparation step, in which a material layer of a metal film or the like is provided on the substrate, and then a resist layer is formed on the material layer; b) an exposure step, in which a portion of the resist layer is irradiated with radiation through a photomask; c) a development step, in which the resist layer irradiated with radiation is developed to remove the unexposed portion; d) a patterning step, in which the material layer of the portion where the resist layer is removed is removed by etching; and e) a stripping step, in which the resist layer is stripped using an alkaline stripping solution. In order to remove the resist material, the alkaline stripping solution used in the process is often a strongly alkaline liquid, and is processed under relatively high temperature conditions.
[0011] At this time, in order to improve the conveying stability of the substrate, a laminate having an adherend such as a semiconductor wafer fixed via an adhesive layer on a support such as a glass substrate can be used as the substrate, but the adhesive layer used in such an application requires high alkali resistance. In addition, sometimes the adhesive layer is also required to have high alkali resistance, and an adhesive layer with high alkali resistance is required.
[0012] However, according to the findings of the present inventors, when patterning using a resist material is performed using the laminate described in Patent Document 1, there is a problem that the adhesion of the adhesive layer decreases when the resist layer is peeled off with an alkaline stripping solution.
[0013] The present invention is completed in view of the above aspects, and its purpose is to provide a composition for forming an adhesive layer that has high alkali resistance and also has laser processability, a laminated body formed by bonding a support body and an adherend using the adhesive layer forming composition, a manufacturing method and a processing method of the laminated body, and a manufacturing method of a laminated body including a patterned material layer.
[0014] [Technical means to solve the problem]
[0015] In order to solve the above-mentioned problems, the present inventors have conducted intensive research and found that the following adhesive layer-forming composition, i.e., an adhesive layer-forming composition comprising an alkali-soluble resin containing an unsaturated group and further comprising a larger amount of an epoxy compound having two or more epoxy groups relative to the alkali-soluble resin containing an unsaturated group, is suitable as an adhesive layer, thereby completing the present invention.
[0016] The reason may not be clear, but can be considered as follows. In the process of making support and adherend adhere via adhesive layer, in order to carry out solvent drying etc., the laminate is heat treated. At this time, the unsaturated groups possessed by the alkali-soluble resin containing unsaturated groups are thermally crosslinked with each other. And then, also carry out the thermal crosslinking of the epoxy group possessed by the alkali-soluble acidic group and epoxy compound for showing the alkali-soluble acidic group possessed by the alkali-soluble resin containing unsaturated groups. Thus, a firm crosslinked structure can be formed, and because more epoxy compounds are included in the composition, the acidic group for showing alkali-soluble is consumed significantly by crosslinking reaction, thereby alkali resistance can be improved. In addition, in order to absorb laser well, the alkali-soluble resin containing unsaturated groups is heated by laser irradiation. Thus, the alkali-soluble resin containing unsaturated groups goes bad, and the adherend can be peeled off, so the laser processability can be improved.
[0017] That is, the above-mentioned problems can be solved by the following structure.
[0018] [1] A composition for forming an adhesive layer, wherein in a laminate including an adhesive layer between a light-transmitting support and an adherend,
[0019] The support and the adherend can be separated from the laminate by irradiating light from the support side, and the adhesive layer-forming composition includes:
[0020] (A) an alkali-soluble resin containing an unsaturated group;
[0021] (B) an epoxy compound having at least two epoxy groups; and
[0022] (D) a solvent,
[0023] The content of the epoxy compound (B) is 25% by mass to 70% by mass based on the total mass of the unsaturated group-containing alkali-soluble resin (A).
[0024] [2] The adhesive layer-forming composition according to [1], wherein
[0025] The (B) epoxy compound has an aromatic ring and / or an alicyclic structure.
[0026] [3] The adhesive layer-forming composition according to [1] or [2], wherein
[0027] The epoxy compound (B)
[0028] The absorbance of light at a wavelength of 266 nm after measuring the absorbance of a 0.001 wt % acetonitrile solution in a quartz cell with an optical path length of 1 cm using an ultraviolet-visible-infrared spectrophotometer is 0.10 or more.
[0029] [4] The composition for forming an adhesive layer according to any one of [1] to [3], wherein
[0030] The weight average molecular weight of the unsaturated group-containing alkali-soluble resin (A) is 1,000 to 40,000,
[0031] The acid value is 20 mgKOH / g to 200 mgKOH / g.
[0032] [5] The adhesive layer-forming composition according to any one of [1] to [4], comprising (C) a polymerizable compound having at least one ethylenically unsaturated bond,
[0033] The content of the (C) polymerizable compound is 1% by mass to 10% by mass based on the total mass of the (A) unsaturated group-containing alkali-soluble resin and the (B) epoxy compound.
[0034] [6] A laminated body comprising:
[0035] Support body;
[0036] adherend; and
[0037] The adhesive layer is disposed between the support and the adherend and includes a coating film or a cured film of the adhesive layer-forming composition according to any one of [1] to [5].
[0038] [7] The laminate according to [6], comprising a resist layer, the resist layer being arranged on a surface of the adherend opposite to a surface on which the adhesive layer is arranged,
[0039] The resist layer is arranged in contact with an adherend, or is arranged so that a material layer is sandwiched between the resist layer and the adherend.
[0040] [8] The laminate according to [6], comprising a material layer, the material layer being arranged on a surface of the adherend opposite to a surface on which the adhesive layer is arranged, and being patterned.
[0041] [9] A method for manufacturing a laminate, comprising:
[0042] A step of forming an adhesive layer on the surface of one or both of a support and an adherend using the adhesive layer-forming composition according to any one of [1] to [5]; and
[0043] a step of bonding the support and the adherend together via the formed adhesive layer.
[0044]
[10] The method for producing a laminate according to [9], comprising the step of providing a resist layer on the adherend,
[0045] The resist layer is arranged on a surface opposite to a surface on which the adhesive layer is arranged.
[0046]
[11] A method for treating a laminate, comprising:
[0047] A step of preparing the laminate according to any one of [6] to [8]; and
[0048] A step of preparing the laminated body;
[0049] The step of irradiating the adhesive layer with light to separate the support and the adherend, in the method for treating the laminate,
[0050] The support transmits light having a wavelength of 10 nm to 400 nm.
[0051]
[12] A method for manufacturing a laminate, wherein the laminate comprises a patterned material layer, the method comprising:
[0052] A step of preparing a laminated body, the laminated body comprising:
[0053] Support body;
[0054] Adhesive body;
[0055] an adhesive layer disposed between the support and the adherend and comprising a coating film or a cured film of the adhesive layer-forming composition according to any one of [1] to [5]; and
[0056] A resist layer is disposed on the surface of the adherend opposite to the surface on which the adhesive layer is disposed and is not exposed;
[0057] an exposure step of irradiating a portion of the resist layer with radiation through a photomask;
[0058] a developing step of developing the resist layer irradiated with radiation to remove the exposed portion or the unexposed portion of the resist layer; and
[0059] In the stripping step, the resist layer is stripped using an alkaline stripping solution.
[0060] [Effects of the Invention]
[0061] According to the present invention, there are provided a composition for forming an adhesive layer having high alkali resistance and also laser processability, a laminate formed by bonding a support body and an adherend using the adhesive layer forming composition, a method for manufacturing and a method for treating the laminate, and a method for manufacturing a laminate comprising a patterned material layer. DETAILED DESCRIPTION
[0062] Hereinafter, the embodiment of the present invention will be described, but the present invention is not limited to the following embodiment. In addition, in the present invention, when the first decimal place is 0, the decimal places may be omitted.
[0063] In addition, the numerical range expressed using "to" in this specification means a range including the numerical values described before and after "to" as the lower limit and the upper limit.
[0064] 1. Adhesive layer forming composition
[0065] The adhesive layer-forming composition of the present embodiment includes:
[0066] (A) an unsaturated group-containing alkali-soluble resin (hereinafter, also referred to as "component (A)");
[0067] (B) an epoxy compound having at least two epoxy groups (hereinafter, also referred to simply as "component (B)"); and
[0068] (D) a solvent (hereinafter, also referred to as "component (D)"),
[0069] The content of the epoxy compound (B) is 25% by mass to 70% by mass based on the total mass of the unsaturated group-containing alkali-soluble resin (A).
[0070] 1-1. (A) Alkali-soluble resin containing unsaturated groups
[0071] (A) component has a polymerizable unsaturated group and an acidic group for showing alkali solubility. As long as it is such a resin, it is not particularly limited and can be widely used. The polymerizable unsaturated groups react with each other, and then the acidic group reacts with the epoxy group of (B) component to form a strong cross-linked structure, and the acidic group for showing alkali solubility is consumed, so that alkali resistance can be improved.
[0072] The polymerizable unsaturated group of the component (A) is not particularly limited as long as it is a functional group having an unsaturated bond, but is preferably a (meth)acryloyl group. The presence of a (meth)acryloyl group can improve curability and impart good alkali resistance.
[0073] In addition, “(meth)acryloyl” is a general term for acryloyl and methacryloyl, “(meth)acrylic acid” is a general term for acrylic acid and methacrylic acid, and “(meth)acrylate” is a general term for acrylate and methacrylate, and all refer to one or both of these.
[0074] Examples of the acidic group that the component (A) has for expressing alkali solubility include a carboxyl group, a phosphoric acid group, and a sulfonic acid group. From the viewpoint of further improving the reactivity with the component (B), a carboxyl group is preferred.
[0075] The (A) component preferably absorbs light well. The (A) component absorbs laser light well and generates heat, and the (A) component deteriorates or decomposes, and the adherend can be peeled off well. The absorbed light is preferably ultraviolet light, more preferably light with a wavelength of 10nm to 400nm, further preferably light with a wavelength of 100nm to 400nm, and most preferably light with a wavelength of 200nm to 400nm.
[0076] From the viewpoint of good absorption of light, the maximum value of the absorbance of light of wavelength 260nm to 400nm of component (A) is preferably 0.10 or more, more preferably 0.10 to 1.50, and further preferably 0.15 to 1.30. If the absorbance is 0.10 or more, it is easy for the adhesive layer to absorb ultraviolet rays, and the deterioration or decomposition of the cured film caused by laser irradiation can be more effectively promoted. If the absorbance is 1.50 or less, the exposure sensitivity can be maintained, so patterning can be performed. Regarding the absorbance, the absorbance of a 0.001 weight% concentration of propylene glycol monomethyl ether acetate (hereinafter also referred to as "PGMEA (propylene glycol monomethyl ether acetate)") solution can be measured in a quartz cell with a light path length of 1 cm using an ultraviolet visible infrared spectrophotometer "UH4150" (manufactured by Hitachi High-Tech Science Co., Ltd.).
[0077] In addition, the acid value of component (A) is preferably 20 mgKOH / g to 200 mgKOH / g, and more preferably 30 mgKOH / g to 150 mgKOH / g. When the acid value is 20 mgKOH / g or more, residue is not easy to remain during alkali development, and when it is 200 mgKOH / g or less, the penetration of the alkali developer does not become too fast, so stripping development can be suppressed. In addition, the acid value can be obtained by titrating with a 1 / 10 N-KOH aqueous solution using a potentiometric titration device "COM-1600" (manufactured by Hiranuma Industry Co., Ltd.).
[0078] In addition, the weight average molecular weight (Mw) of component (A) measured by gel permeation chromatography (GPC) (HLC-8220GPC, manufactured by Tosoh Co., Ltd.) in terms of polystyrene is usually preferably 1000 to 100000, more preferably 1500 to 30000, and further preferably 2000 to 15000. When the weight average molecular weight (Mw) is 1000 or more, the adhesion between the support and the adherend can be improved. In addition, when the weight average molecular weight (Mw) is less than 100000, it is easy to adjust the solution viscosity of the photosensitive resin composition suitable for coating, and it will not take too much time when coating the surface of the support or the adherend.
[0079] Hereinafter, exemplary compounds of the component (A) preferably used in the adhesive layer-forming composition of the present embodiment are listed, but the present invention is not limited to the following compounds.
[0080] 1-1-1. Exemplary compound 1 of component (A)
[0081] The component (A) is preferably an alkali-soluble resin containing a polymerizable unsaturated group obtained by reacting a reaction product of an epoxy compound having two or more epoxy groups with (meth) acrylic acid and further reacting with a polybasic acid carboxylic acid or its anhydride. When the alkali-soluble resin is produced, a polyester is generated by the reaction of a hydroxyl group with a polybasic acid carboxylic acid, but its average degree of polymerization is preferably a low molecular weight of about 2 to 500.
[0082] The epoxy compound is preferably an epoxy compound having two or more epoxy groups. Examples of such epoxy compounds include: bisphenol A type epoxy compounds, bisphenol F type epoxy compounds, bisphenol fluorene type epoxy compounds, phenol novolac type epoxy compounds, cresol novolac type epoxy compounds (e.g., EPPN-501H: manufactured by Nippon Kayaku Co., Ltd.), phenol aralkyl type epoxy compounds, phenol novolac compounds containing a naphthalene skeleton (e.g., NC-7000L: manufactured by Nippon Kayaku Co., Ltd.), biphenyl type epoxy compounds (e.g., jER YX4000: manufactured by Mitsubishi Chemical Co., Ltd.), naphthol aralkyl type epoxy compounds, trisphenol methane type epoxy compounds, tetraphenol ethane type epoxy compounds, glycidyl ethers of polyols, glycidyl esters of polycarboxylic acids, copolymers of monomers having (meth)acrylic acid groups containing glycidyl (meth)acrylate as units represented by copolymers of methacrylic acid and glycidyl methacrylate, 3',4'-epoxycyclohexylmethyl 3,4-epoxycyclohexanecarboxylate (e.g., Celloxide 2021P: manufactured by Daicel Co., Ltd.), butanetetracarboxylic acid tetra(3,4-epoxycyclohexylmethyl) modified ε-caprolactone (e.g., EPOLEAD )GT401: manufactured by Daicel Co., Ltd.), epoxy compounds having an epoxy cyclohexyl group represented by HiREM-1 manufactured by Shikoku Chemical Industry Co., Ltd., multifunctional epoxy compounds having a dicyclopentadiene skeleton (for example, HP7200 series: manufactured by DIC Co., Ltd.), 1,2-epoxy-4-(2-oxacyclopropyl)cyclohexane adduct of 2,2-bis(hydroxymethyl)-1-butanol (for example, EHPE3150: manufactured by Daicel Co., Ltd.), epoxidized polybutadiene (for example, NISSO-PB·JP-100: manufactured by Nippon Soda Co., Ltd.), and epoxy compounds having a silicone skeleton, etc.
[0083] From the perspective of further improving the alkali resistance of the cured film, it is preferred that the (A) component has at least one aromatic ring and alicyclic structure in the molecule. By setting such a structure, even if the same addition amount is used, it is easy to improve the alkali resistance. The (A) component is more preferably an alkali-soluble resin having multiple aromatic rings, and more preferably an alkali-soluble resin having a repeating unit containing a fluorene structure, and more preferably an alkali-soluble resin having a repeating unit containing a diaryl fluorene skeleton. For example, the (A) component having a repeating unit containing a diaryl fluorene skeleton is preferably a resin represented by the following general formula (1).
[0084] [Chemistry 1]
[0085]
[0086] In formula (1), Ar is independently an aromatic hydrocarbon group having 6 to 14 carbon atoms, and a portion of the bonded hydrogen atoms may be substituted by a substituent selected from the group consisting of an alkyl group having 1 to 10 carbon atoms, an aryl group or an arylalkyl group having 6 to 10 carbon atoms, a cycloalkyl group or a cycloalkylalkyl group having 3 to 10 carbon atoms, an alkoxy group having 1 to 5 carbon atoms, and a halogen group. R1 is independently an alkylene group having 2 to 4 carbon atoms, and l is independently a number from 0 to 3. G is independently a (meth)acryloyl group, a substituent represented by the following general formula (2) or the following general formula (3), and Y is a tetravalent carboxylic acid residue. Z is independently a hydrogen atom or a substituent represented by the following general formula (4), and one or more of them are substituents represented by the following general formula (4). n is a number having an average value of 1 to 20.
[0087] [Chemistry 2]
[0088]
[0089] [Chemistry 3]
[0090]
[0091] In formula (2) and formula (3), R2 is a hydrogen atom or a methyl group, R3 is a divalent alkylene group or an alkylarylene group having 2 to 10 carbon atoms, R4 is a divalent saturated hydrocarbon group or a divalent unsaturated hydrocarbon group having 2 to 20 carbon atoms, and p is a number from 0 to 10. * indicates a bonding site.
[0092] [Chemistry 4]
[0093]
[0094] In formula (4), W is a divalent or trivalent carboxylic acid residue, and m is a number of 1 or 2. * represents a bonding site.
[0095] In addition, Y represented by the general formula (1) preferably includes at least one aromatic hydrocarbon group. Examples of aromatic hydrocarbon groups include: phenyl, biphenyl, benzophenone, naphthyl, biphenyl ether, etc. Among the aromatic hydrocarbon groups, biphenyl, benzophenone, or naphthyl is preferred. If Y is an aromatic hydrocarbon group, the absorbance of the resin at a wavelength of 260nm to 400nm can be increased, and the deterioration or decomposition of the cured film caused by laser irradiation can be more effectively promoted.
[0096] Next, a method for producing the unsaturated group-containing alkali-soluble resin (A) represented by the general formula (1) will be described in detail.
[0097] First, (meth)acrylic acid, any one of the (meth)acrylic acid derivatives represented by the following general formula (6) or the following general formula (7), or both are reacted with an epoxy compound (a-1) having a bisarylfluorene skeleton represented by the following general formula (5) which may have several oxyalkylene groups in one molecule (hereinafter, also referred to as "epoxy compound (a-1)") to obtain a diol compound as epoxy (meth)acrylate. In addition, the bisarylfluorene skeleton is preferably a bisnaphtholfluorene skeleton or a bisphenolfluorene skeleton.
[0098] [Chemistry 5]
[0099]
[0100] In formula (5), Ar is independently an aromatic hydrocarbon group having 6 to 14 carbon atoms, and a part of the bonded hydrogen atoms may be substituted by an alkyl group having 1 to 10 carbon atoms, an aryl group or an arylalkyl group having 6 to 10 carbon atoms, a cycloalkyl group or a cycloalkylalkyl group having 3 to 10 carbon atoms, an alkoxy group having 1 to 5 carbon atoms, or a halogen group. R1 is independently an alkylene group having 2 to 4 carbon atoms, and l is independently a number of 0 to 3.
[0101] [Chemistry 6]
[0102]
[0103] [Chemistry 7]
[0104]
[0105] In formula (6) and formula (7), R2 is a hydrogen atom or a methyl group, R3 is a divalent alkylene group or an alkyl arylene group having 2 to 10 carbon atoms, R4 is a divalent saturated hydrocarbon group or a divalent unsaturated hydrocarbon group having 2 to 20 carbon atoms, and p is a number from 0 to 10.
[0106] The reaction of the epoxy compound (a-1) with the (meth) acrylic acid or (meth) acrylic acid derivative can be carried out using a known method. For example, the following is recorded in Japanese Patent Laid-Open No. 4-355450: By using about 2 moles of (meth) acrylic acid relative to 1 mole of an epoxy compound having two epoxy groups, a diol compound containing a polymerizable unsaturated group can be obtained. In this embodiment, the compound obtained by the reaction is a diol (d) containing a polymerizable unsaturated group represented by formula (8) (hereinafter, also referred to as "diol (d) represented by general formula (8)").
[0107] [Chemistry 8]
[0108]
[0109] In formula (8), Ar is independently an aromatic hydrocarbon group having 6 to 14 carbon atoms, and a part of the bonded hydrogen atoms may be substituted by an alkyl group having 1 to 10 carbon atoms, an aryl group or an arylalkyl group having 6 to 10 carbon atoms, a cycloalkyl group or a cycloalkylalkyl group having 3 to 10 carbon atoms, an alkoxy group having 1 to 5 carbon atoms, or a halogen group. G is independently a (meth)acryloyl group, a substituent represented by the following general formula (2) or the following general formula (3), R1 is independently an alkylene group having 2 to 4 carbon atoms, and l is independently a number from 0 to 3.
[0110] [Chemistry 9]
[0111]
[0112] [Chemistry 10]
[0113]
[0114] In formula (2) and formula (3), R2 is a hydrogen atom or a methyl group, R3 is a divalent alkylene group or an alkylarylene group having 2 to 10 carbon atoms, R4 is a divalent saturated hydrocarbon group or a divalent unsaturated hydrocarbon group having 2 to 20 carbon atoms, and p is a number from 0 to 10. * indicates a bonding site.
[0115] In the synthesis of the diol (d) represented by the general formula (8) and the subsequent production of the unsaturated group-containing alkali-soluble resin represented by the general formula (1) by reacting a polycarboxylic acid or anhydride thereof, the reaction is usually carried out in a solvent using a catalyst as needed.
[0116] Examples of the solvent include: cellosolve-based solvents such as ethyl cellosolve acetate and butyl cellosolve acetate; high-boiling-point ether-based or ester-based solvents such as diethylene glycol dimethyl ether (diglyme), ethyl carbitol acetate, butyl carbitol acetate, and propylene glycol monomethyl ether acetate; ketone-based solvents such as cyclohexanone and diisobutyl ketone, etc. In addition, there are no particular restrictions on the reaction conditions of the solvent, catalyst, etc. used, and for example, it is preferred to use a solvent that does not have a hydroxyl group and has a boiling point higher than the reaction temperature as a reaction solvent.
[0117] In the reaction between the epoxy group and the carboxyl group or the hydroxyl group, a catalyst is preferably used. Japanese Patent Application Laid-Open No. 9-325494 describes ammonium salts such as tetraethylammonium bromide and triethylbenzylammonium chloride; and phosphines such as triphenylphosphine and tri(2,6-dimethoxyphenyl)phosphine.
[0118] Next, the diol (d) represented by the general formula (8) obtained by the reaction of the epoxy compound (a-1) and the (meth)acrylic acid derivative is reacted with a dicarboxylic acid or a tricarboxylic acid or an anhydride thereof (b), a tetracarboxylic acid or an anhydride thereof (c), to obtain an alkali-soluble resin having a carboxyl group and a polymerizable unsaturated group in one molecule represented by the following general formula (1).
[0119] [Chemistry 11]
[0120]
[0121] In formula (1), Ar is independently an aromatic hydrocarbon group having 6 to 14 carbon atoms, and a portion of the bonded hydrogen atoms may be substituted by an alkyl group having 1 to 10 carbon atoms, an aryl group or an arylalkyl group having 6 to 10 carbon atoms, a cycloalkyl group or a cycloalkylalkyl group having 3 to 10 carbon atoms, an alkoxy group having 1 to 5 carbon atoms, or a halogen group. R1 is independently an alkylene group having 2 to 4 carbon atoms, and l is independently a number from 0 to 3. G is independently a (meth)acryloyl group, a substituent represented by the following general formula (2) or the following general formula (3), and Y is a tetravalent carboxylic acid residue. Z is independently a hydrogen atom or a substituent represented by the following general formula (4), and one or more of them are substituents represented by the following general formula (4). n is a number having an average value of 1 to 20.
[0122] [Chemistry 12]
[0123]
[0124] [Chemistry 13]
[0125]
[0126] In formula (2) and formula (3), R2 is a hydrogen atom or a methyl group, R3 is a divalent alkylene group or an alkylarylene group having 2 to 10 carbon atoms, R4 is a divalent saturated hydrocarbon group or a divalent unsaturated hydrocarbon group having 2 to 20 carbon atoms, and p is a number from 0 to 10. * indicates a bonding site.
[0127] [Chemistry 14]
[0128]
[0129] In formula (4), W is a divalent or trivalent carboxylic acid residue, and m is 1 or 2. * represents a bonding site.
[0130] The acid component used to synthesize the alkali-soluble resin containing unsaturated groups represented by the general formula (1) is a polyacid component that can react with the hydroxyl group in the diol (d) molecule represented by the general formula (8), preferably a dicarboxylic acid or a tricarboxylic acid or their acid monoanhydride (b) and a tetracarboxylic acid or its acid dianhydride (c) are used in combination. The carboxylic acid residue of the acid component can be any of a saturated hydrocarbon group or an unsaturated hydrocarbon group. In addition, these carboxylic acid residues can also contain bonds containing heterogeneous elements such as -O-, -S-, and carbonyl groups.
[0131] Examples of the dicarboxylic acid or tricarboxylic acid or their monoanhydrides (b) include chain hydrocarbon dicarboxylic acids or tricarboxylic acids, alicyclic hydrocarbon dicarboxylic acids or tricarboxylic acids, aromatic hydrocarbon dicarboxylic acids or tricarboxylic acids, or their monoanhydrides.
[0132] Examples of the monoanhydride of the chain hydrocarbon dicarboxylic acid or tricarboxylic acid include monoanhydrides of succinic acid, acetylsuccinic acid, maleic acid, adipic acid, itaconic acid, azelaic acid, citramalic acid, malonic acid, glutaric acid, citric acid, tartaric acid, oxoglutaric acid, pimelic acid, sebacic acid, suberic acid, diglycolic acid, and monoanhydrides of dicarboxylic acids or tricarboxylic acids into which any substituent is introduced.
[0133] Examples of the monoanhydride of alicyclic hydrocarbon dicarboxylic acid or tricarboxylic acid include monoanhydrides of cyclobutanedicarboxylic acid, cyclopentanedicarboxylic acid, hexahydrophthalic acid, 1,2,3,6-tetrahydrophthalic acid, norbornanedicarboxylic acid, and monoanhydrides of dicarboxylic acids or tricarboxylic acids into which any substituent is introduced.
[0134] Examples of the monoanhydride of the aromatic hydrocarbon dicarboxylic acid or tricarboxylic acid include monoanhydrides of phthalic acid, isophthalic acid, trimellitic acid, 1,8-naphthalene dicarboxylic acid, 2,3-naphthalene dicarboxylic acid, and monoanhydrides of dicarboxylic acids or tricarboxylic acids into which any substituent is introduced.
[0135] Among the acid monoanhydrides of dicarboxylic acids or tricarboxylic acids, preferred are acid monoanhydrides of succinic acid, itaconic acid, 1,2,3,6-tetrahydrophthalic acid, hexahydrotrimellitic acid, phthalic acid, trimellitic acid, 1,8-naphthalenedicarboxylic acid, 2,3-naphthalenedicarboxylic acid, and the like; more preferred are acid monoanhydrides of 1,2,3,6-tetrahydrophthalic acid, 1,8-naphthalenedicarboxylic acid, 2,3-naphthalenedicarboxylic acid, and the like.
[0136] In addition, among dicarboxylic acids or tricarboxylic acids, it is preferred to use their acid monoanhydrides. The acid monoanhydrides of the dicarboxylic acids or tricarboxylic acids may be used alone or in combination of two or more.
[0137] Examples of the tetracarboxylic acid or its dianhydride (c) include chain hydrocarbon tetracarboxylic acids, alicyclic hydrocarbon tetracarboxylic acids, aromatic hydrocarbon tetracarboxylic acids, or dianhydrides thereof.
[0138] Examples of the chain hydrocarbon tetracarboxylic acid include butane tetracarboxylic acid, pentane tetracarboxylic acid, hexane tetracarboxylic acid, and chain hydrocarbon tetracarboxylic acids into which a substituent such as an alicyclic hydrocarbon group or an unsaturated hydrocarbon group is introduced.
[0139] Examples of the alicyclic hydrocarbon tetracarboxylic acid include cyclobutane tetracarboxylic acid, cyclopentane tetracarboxylic acid, cyclohexane tetracarboxylic acid, cycloheptane tetracarboxylic acid, norbornane tetracarboxylic acid, and alicyclic hydrocarbon tetracarboxylic acids into which a substituent such as a chain hydrocarbon group or an unsaturated hydrocarbon group is introduced.
[0140] Examples of the aromatic hydrocarbon tetracarboxylic acid include pyromellitic acid, benzophenonetetracarboxylic acid, 3,3′,4,4′-biphenyltetracarboxylic acid, diphenyl ether tetracarboxylic acid, diphenyl sulfone tetracarboxylic acid, naphthalene-1,4,5,8-tetracarboxylic acid, and naphthalene-2,3,6,7-tetracarboxylic acid.
[0141] In addition, bis-trimellitic anhydride aryl esters can also be used. The so-called bis-trimellitic anhydride aryl esters are, for example, a group of compounds produced by the method described in International Publication No. 2010 / 074065, and are acid dianhydrides in the form of ester bonds formed by the reaction of two hydroxyl groups of aromatic diols (naphthalene diol, biphenol, terphenyl diol, etc.) with the carboxyl groups of two molecules of trimellitic anhydride. Hereinafter, these compounds are recorded as bis-trimellitic anhydride esters of aromatic diols.
[0142] Among the tetracarboxylic acids or their dianhydrides, 3,3',4,4'-biphenyltetracarboxylic acid, benzophenonetetracarboxylic acid, diphenyl ether tetracarboxylic acid, naphthalene-1,4,5,8-tetracarboxylic acid, and naphthalene-2,3,6,7-tetracarboxylic acid are preferred, and 3,3',4,4'-biphenyltetracarboxylic acid, benzophenonetetracarboxylic acid, naphthalene-1,4,5,8-tetracarboxylic acid, and naphthalene-2,3,6,7-tetracarboxylic acid are more preferred. In addition, among the tetracarboxylic acids or their dianhydrides, their dianhydrides are preferably used. Furthermore, the bis-trimellitic anhydride ester of naphthalenediol can also be preferably used. In addition, the tetracarboxylic acids or their dianhydrides, and the bis-trimellitic anhydride ester of aromatic diols can be used alone or in combination of two or more.
[0143] The reaction of the diol (d) represented by the general formula (8) with the acid component (b) and the acid component (c) is not particularly limited, and a known method can be used. For example, Japanese Patent Laid-Open No. 9-325494 describes a method of reacting (meth)acrylate epoxy ester with tetracarboxylic dianhydride at a reaction temperature of 90° C. to 140° C.
[0144] Here, in order to make the terminal of the compound a carboxyl group, it is preferred to react so that the molar ratio of the diol (d) represented by the general formula (8), the dicarboxylic acid or tricarboxylic acid or their monoanhydride (b), and the tetracarboxylic acid or its dianhydride (c) becomes (d):(b):(c)=1.0:0.01 to 1.0:0.2 to 1.0.
[0145] For example, when an acid monoanhydride (b) or an acid dianhydride (c) is used, it is preferred to react such that the molar ratio of the diol (d) containing a polymerizable unsaturated group relative to the amount of the acid component [(b) / 2+(c)] [[(b) / 2+(c)] / (d)] is 0.5 to 1.0. Here, when the molar ratio is 0.5 or more, the content of the unreacted diol containing a polymerizable unsaturated group will not increase, and thus the temporal stability of the alkali-soluble resin composition can be improved. On the other hand, when the molar ratio is 1.0 or less, since the end of the alkali-soluble resin represented by the general formula (1) does not become an acid anhydride, the increase in the content of the unreacted acid dianhydride can be suppressed, and thus the temporal stability of the alkali-soluble resin composition can be improved. In addition, the molar ratio of each component of (b), (c) and (d) can be arbitrarily changed within the above range for the purpose of adjusting the acid value and molecular weight of the alkali-soluble resin represented by the general formula (1).
[0146] In the adhesive layer forming composition of the present embodiment, the content of the alkali-soluble resin containing unsaturated groups (A) represented by the general formula (1) is preferably 10% to 80% by mass, more preferably 30% to 80% by mass, and further preferably 50% to 80% by mass, relative to the total mass of the solid component. If the content of the (A) component is more than 10% by mass relative to the total mass of the solid component, it is easy to absorb the irradiated light (such as ultraviolet rays) and deteriorate, so the support can be easily separated from the adherend. In addition, if it is less than 80% by mass, the acidic group used to show alkali solubility can be fully consumed by the cross-linking reaction with the (B) component, so that the alkali resistance can be improved.
[0147] In addition, the acid value of the unsaturated group-containing alkali-soluble resin (A) represented by the general formula (1) is preferably 20 mgKOH / g to 200 mgKOH / g, and more preferably 30 mgKOH / g to 150 mgKOH / g. When the acid value is 20 mgKOH / g or more, residue is not easy to remain during alkali development, and when it is 200 mgKOH / g or less, the penetration of the alkali developer does not become too fast, so stripping development can be suppressed. In addition, the acid value can be obtained by titrating with a 1 / 10N-KOH aqueous solution using a potentiometric titration device "COM-1600" (manufactured by Hiranuma Industry Co., Ltd.).
[0148] In addition, the weight average molecular weight (Mw) of the polystyrene conversion obtained by gel permeation chromatography (GPC) determination (HLC-8220GPC, manufactured by Tosoh Co., Ltd.) of the alkali-soluble resin containing unsaturated groups (A) represented by the general formula (1) is usually preferably 1000 to 100000, more preferably 1500 to 30000, and further preferably 2000 to 15000. When the weight average molecular weight (Mw) is more than 1000, the adhesion between the support and the adherend can be improved. In addition, when the weight average molecular weight (Mw) is less than 100000, it is easy to adjust to the solution viscosity of the photosensitive resin composition suitable for coating, and it will not take too much time when coating on the surface of the support or the adherend.
[0149] 1-1-2. Exemplary compound 2 of component (A)
[0150] As the component (A), a (meth)acrylic acid copolymer is also preferably used.
[0151] The component (A) may be, for example, a (meth)acrylic acid copolymer composed of any one or all of the following structural units (AA) to (AE) derived from different monomers. The (meth)acrylic acid copolymer may include structural units (AB) and (AC) or structural unit (AD).
[0152] (AA) Structural unit having an ultraviolet absorbing group
[0153] (AB) Structural unit having a polymerizable unsaturated group and no carboxyl group
[0154] (AC) Structural unit having a carboxyl group and no polymerizable unsaturated group
[0155] (AD) Structural unit having a polymerizable unsaturated group and a carboxyl group
[0156] (AE) A structural unit having no ultraviolet absorbing group, polymerizable unsaturated group, or carboxyl group
[0157] The structural unit (AA) is a structural unit having an ultraviolet absorbing group, and the (meth)acrylic copolymer preferably contains the structural unit (AA). By containing the structural unit (AA), light can be well absorbed and laser stripping properties can be improved. The structural unit (AA) may have the ultraviolet absorbing group in the main chain of the (meth)acrylic copolymer or in the side chain, but from the viewpoint of ease of manufacturing the (meth)acrylic copolymer, it is preferably in the side chain.
[0158] Furthermore, from the viewpoint of improving the ultraviolet absorption capacity of the (meth)acrylic copolymer, the structural unit (AA) is preferably a structural unit derived from a monomer having a molar absorption coefficient of 3000 L / (mol·cm) or more at a wavelength of 355 nm. From the same viewpoint, the structural unit (AA) is more preferably a structural unit derived from a monomer having a molar absorption coefficient of 3000 L / (mol·cm) to 100000 L / (mol·cm) at a wavelength of 355 nm, further preferably a structural unit derived from a monomer having a molar absorption coefficient of 4000 L / (mol·cm) to 90000 L / (mol·cm), and particularly preferably a structural unit derived from a monomer having a molar absorption coefficient of 5000 L / (mol·cm) to 80000 L / (mol·cm). The molar absorption coefficient can be calculated by measuring the absorbance of a 0.001 wt % acetonitrile solution in a quartz cell with an optical path length of 1 cm using an ultraviolet-visible-infrared spectrophotometer "UH4150" (manufactured by Hitachi High-Tech Science Co., Ltd.) and dividing the result by the molar concentration.
[0159] The ultraviolet absorbing group includes a functional group having the following structure, etc.: a benzotriazole structure, a benzophenone structure in which a part of the hydrogen atoms contained in the benzene ring is substituted with a hydroxyl group (hereinafter, also referred to as a "substituted benzophenone structure"), a triazine structure, a salicylic acid structure, a benzoate structure, a cinnamic acid derivative structure, a diphenyl sulfoxide structure, a diphenyl sulfone structure, a diphenyl structure, a diphenylamine structure, a naphthalene derivative structure, a structure based on anthracene and its derivatives, a structure having a dinaphthalene structure, and a structure having a phenanthroline structure. Among these, in terms of efficiently absorbing ultraviolet rays of 355nm, a functional group having a benzotriazole structure, a substituted benzophenone structure or a triazine structure is preferred, a functional group having a benzotriazole structure or a triazine structure is more preferred, and a functional group having a benzotriazole structure (hydroxyphenylbenzotriazole structure) is further preferred.
[0160] Examples of the functional group having a benzotriazole structure include those derived from 2-(2'-hydroxy-phenyl)benzotriazole, 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-5'-tert-butylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)benzotriazole, 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)-5- Functional groups in the structures of compounds such as chlorobenzotriazole, 2-(2'-hydroxy-3',5'-di-tert-amylphenyl)benzotriazole, 2-(2'-hydroxy-4'-octyloxyphenyl)benzotriazole, 2-{2'-hydroxy-3'-(3",4",5",6"-tetrahydrophthalimidomethyl)-5'-methylphenyl}benzotriazole, and C7-C9-alkyl-3-[3-(2H-benzotriazol-2-yl)-5-(1,1-dimethylethyl)-4-hydroxyphenyl]propyl ether.
[0161] Examples of the functional group having a substituted benzophenone structure include a functional group having a structure derived from a compound such as 4-dihydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2,2'-dihydroxy-4-methoxybenzophenone, 2-hydroxy-4-methoxy-2'-carboxybenzophenone, 2-hydroxy-4-methoxy-5-sulfobenzophenone trihydrate, 2,2'-dihydroxy-4,4'-dimethoxybenzophenone, 2-hydroxy-4-octyloxybenzophenone, 2-hydroxy-4-octadecyloxybenzophenone, sodium 2,2'-dihydroxy-4,4'-dimethoxy-5-sulfobenzophenone, 2,2',4,4'-tetrahydroxybenzophenone, 4-dodecyloxy-2-hydroxybenzophenone, 5-chloro-2-hydroxybenzophenone, and hydroxydodecylbenzophenone.
[0162] Examples of the functional group having a triazine structure include functional groups having a structure derived from compounds such as 2,4-bis(2,4-dimethylphenyl)-6-(2-hydroxy-4-isooctyloxyphenyl)-1,3,5-triazine, 2-[4-((2-hydroxy-3-dodecyloxypropyl)-oxy)-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine, 2-[4-((2-hydroxy-3-tridecyloxypropyl)-oxy)-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine, and 2-(2,4-dihydroxyphenyl)-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine.
[0163] Furthermore, it is preferred that the structural unit (AA) does not have a polymerizable unsaturated group. Furthermore, it is preferred that the structural unit (AA) does not have a carboxyl group.
[0164] The structural unit (AB) is a structural unit having a polymerizable unsaturated group. However, in the present specification, a structural unit having both a polymerizable unsaturated group and a carboxyl group is a structural unit (AD), and is not included in the structural unit (AB).
[0165] Examples of the polymerizable unsaturated group include a vinyl group, an allyl group, and a (meth)acryloyl group, etc. Among these, a (meth)acryloyl group is preferred.
[0166] The polymerizable unsaturated group is preferably grafted to the side chain in the structural unit (AB). In other words, the polymerizable unsaturated group is preferably bonded to the side chain in the structural unit (AB) via a linking group or a linking structure generated during grafting. Examples of the linking group or the linking structure include: an ester bond, a carbamate bond, and an epoxy acrylate residue. Among these, in terms of ease of grafting, the polymerizable unsaturated group is preferably grafted to the side chain via a carbamate bond or an epoxy acrylate residue. In terms of further improving the compatibility of the (meth)acrylic copolymer with other alkali-soluble resins (for example, an alkali-soluble resin having a fluorene skeleton), the polymerizable unsaturated group is preferably grafted to the side chain via a carbamate bond, and in terms of easier adjustment of the development speed, the polymerizable unsaturated group is preferably grafted to the side chain via an epoxy acrylate residue.
[0167] Furthermore, it is preferred that the structural unit (AB) has no ultraviolet absorbing group.
[0168] The structural unit (AC) is a structural unit having a carboxyl group. However, in the present specification, a structural unit having both a carboxyl group and a polymerizable unsaturated group is a structural unit (AD), and is not included in the structural unit (AC).
[0169] The carboxyl group may be a functional group derived from a monomer (such as (meth) acrylic acid, etc.) of the material serving as the structural unit (AC), or may be grafted to a side chain in the structural unit (AC). In other words, the carboxyl group may be bonded to the side chain in the structural unit (AC) via a linking group or a linking structure generated during grafting. From the perspective of making it easier to adjust the development speed, the carboxyl group is preferably grafted to the side chain in the structural unit (AC). Examples of the linking group or the linking structure include: an ester bond, a carbamate bond, and an epoxy acrylate residue. Among these, from the perspective of ease of grafting, the carboxyl group is preferably grafted to the side chain via a carbamate bond or an epoxy acrylate residue, and from the perspective of making the development speed faster, the carboxyl group is preferably grafted to the side chain via an ester bond.
[0170] Furthermore, it is preferred that the structural unit (AC) does not have an ultraviolet absorbing group.
[0171] The structural unit (AD) is a structural unit having a polymerizable unsaturated group and a carboxyl group. The polymerizable unsaturated group is the functional group described in the structural unit (AB).
[0172] The polymerizable unsaturated group and the carboxyl group are preferably grafted to the side chain in the structural unit (AD). In other words, the polymerizable unsaturated group is preferably bonded to the side chain in the structural unit (AD) via a linking group or a linking structure generated during grafting. Examples of the linking group or the linking structure include: ester bonds, carbamate bonds, and epoxy acrylate residues. For example, after the skeleton of the structural unit (AD) is formed by copolymerization of monomers having a glycidyl group or an alicyclic epoxy group, monomers having a polymerizable unsaturated group and a carboxyl group are reacted, and the polymerizable unsaturated group is grafted by the formation of epoxy acrylate. Furthermore, the structural unit (AD) can be formed by reacting a polycarboxylic acid or its anhydride with a hydroxyl group generated by the formation of epoxy acrylate to graft the carboxyl group. In the structural unit (AD) thus formed, the polymerizable unsaturated group and the carboxyl group are grafted to the side chain via the epoxy acrylate residue, and the carboxyl group is grafted to the side chain via an ester bond. Grafting via an ester bond or a urethane bond can also be performed by a known method.
[0173] The structural unit (AE) is a structural unit arbitrarily introduced for the purpose of adjusting the molecular weight, adjusting the amount of each functional group such as an ultraviolet absorbing group, a polymerizable unsaturated group and a carboxyl group, and the like.
[0174] The structural unit (AE) may be a structural unit derived from a monomer not having the above functional groups. In order to adjust the physical properties of the (meth)acrylic copolymer, a structural unit to which a functional group different from the above functional groups is grafted may be used.
[0175] In addition, each structural unit may be modified with an alkylene oxide or a lactone.
[0176] The (meth)acrylic copolymer may be a copolymer in which the structural unit (AB) and the structural unit (AC) are essential structural units and optionally contains the structural unit (AD) and the structural unit (AE), or may be a copolymer in which the structural unit (AD) is an essential structural unit and optionally contains the structural unit (AB), the structural unit (AC), and the structural unit (AE). A (meth)acrylic copolymer in which the structural unit (AB) and the structural unit (AC) are essential structural units does not require a step for introducing the structural unit (AD), and is therefore easy to synthesize. A (meth)acrylic copolymer in which the structural unit (AD) is an essential structural unit makes it easy to adjust the amount of each functional group provided by the structural unit (AD), thereby making it easy to adjust the development speed, etc.
[0177] The weight average molecular weight (Mw) of the (meth) acrylic copolymer is preferably 1000 to 100000, more preferably 5000 to 70000, and further preferably 10000 to 50000. If the weight average molecular weight (Mw) is 1000 or more, the adhesion when used as an adhesive layer forming composition can be improved. In addition, if the weight average molecular weight (Mw) is 100000 or less, it is easy to adjust the solution viscosity of the curable composition suitable for coating, and it can be coated in a short time, and it is easy to improve the adhesion. The weight average molecular weight (Mw) of the (meth) acrylic copolymer can be set to a polystyrene conversion value obtained by gel permeation chromatography (GPC) measurement (HLC-8220GPC, manufactured by Tosoh Co., Ltd.).
[0178] In addition, the ratio of the structural unit (AA) in the (meth) acrylic copolymer relative to 100 mol% of all structural units is preferably 0.1 mol% to 90 mol%, more preferably 0.1 mol% to 89 mol%, further preferably 1 mol% to 85 mol%, and particularly preferably 5 mol% to 80 mol%. By setting the ratio of the structural unit (AA) to 0.1 mol% or more, it is easy to make the cured film absorb ultraviolet rays, and the deterioration or decomposition of the cured film caused by the irradiation of 355nm laser can be more effectively promoted. By setting the ratio of the structural unit (A) to 90 mol% or less, the amount of functional groups other than the ultraviolet absorbing group contained in the (meth) acrylic copolymer can be increased, and the hardness or alkali solubility of the adhesive layer can be fully improved.
[0179] In addition, the maximum value of the absorbance of light of wavelength 260nm to 400nm of the (meth) acrylic copolymer is preferably 0.10 or more, more preferably 0.10 to 1.50, and further preferably 0.15 to 1.30. If the absorbance is 0.10 or more, it is easy for the adhesive layer to absorb ultraviolet rays, which can more effectively promote the deterioration or decomposition of the cured film caused by laser irradiation. If the absorbance is 1.50 or less, the exposure sensitivity can be maintained, so patterning can be performed. The absorbance can be measured in the same manner as the molar absorption coefficient measurement conditions.
[0180] The acid value of the (meth)acrylic acid copolymer is preferably 20 mgKOH / g to 200 mgKOH / g, more preferably 30 mgKOH / g to 180 mgKOH / g, and further preferably 50 mgKOH / g to 150 mgKOH / g. By setting the acid value to 20 mgKOH / g or more, it is not easy to leave residue during alkali development. By setting the acid value to 200 mgKOH / g or less, the penetration of the alkali developer into the composition can be appropriately adjusted to suppress the stripping development caused by the rapid penetration of the alkali developer. The acid value can be obtained by titrating with a 1 / 10N-KOH aqueous solution using a potentiometric titration device "COM-1600" (manufactured by Hiranuma Industry Co., Ltd.).
[0181] From the same viewpoint, the ratio of the structural unit having a carboxyl group in the (meth)acrylic acid copolymer to 100 mol% of all structural units (the ratio of the total amount of the structural unit (AC) and the structural unit (AD)) is preferably 3 mol% to 50 mol%, more preferably 5 mol% to 45 mol%, and even more preferably 7 mol% to 40 mol%.
[0182] The acrylic acid equivalent of the (meth)acrylic acid copolymer is preferably 300 g / eq to 3000 g / eq, more preferably 350 g / eq to 2500 g / eq, and even more preferably 400 g / eq to 2000 g / eq. By setting the acrylic acid equivalent to 300 g / eq or more, it is easy to incorporate the ultraviolet absorbing group and the carboxyl group into the same molecule. By setting the acrylic acid equivalent to 3000 g / eq or less, the sensitivity can be ensured even at low exposure, and a good development pattern can be formed.
[0183] From the same viewpoint, the ratio of the structural unit having a polymerizable unsaturated group in the (meth)acrylic copolymer to 100 mol% of all structural units (the ratio of the total amount of the structural unit (AB) and the structural unit (AD)) is preferably 3 mol% to 90 mol%, more preferably 5 mol% to 85 mol%, and even more preferably 7 mol% to 80 mol%.
[0184] The equivalent weight of the ultraviolet absorbing group, the acid value, the acrylic acid equivalent and the ratio of each structural unit of the (meth)acrylic copolymer can be adjusted by the copolymerization ratio when copolymerizing the above-mentioned monomers.
[0185] For example, the (meth)acrylic copolymer may be a copolymer having the following structural units at the following ratios: The following ratios are ratios (in mol %) of each structural unit relative to 100 mol % of all structural units in the (meth)acrylic copolymer.
[0186] Structural unit (AA) 0.1 mol% to 80 mol%,
[0187] Structural unit (AB) 5 mol% to 70 mol%,
[0188] Structural unit (AC) 3 mol% to 50 mol%,
[0189] Preferably
[0190] Structural unit (AA) 6 mol% to 70 mol%,
[0191] Structural unit (AB) 10 mol% to 60 mol%,
[0192] Structural unit (AC) 5 mol% to 45 mol%.
[0193] Structural unit (AA) 0.1 mol% to 80 mol%,
[0194] Structural unit (AB) 0.001 mol% to 70 mol%,
[0195] Structural unit (AD) 3 mol% to 50 mol%,
[0196] Preferably
[0197] Structural unit (AA) 6 mol% to 70 mol%,
[0198] Structural unit (AB) 0.1 mol% to 60 mol%,
[0199] Structural unit (AD) 5 mol% to 45 mol%,
[0200] More preferably
[0201] Structural unit (AA) 16 mol% to 60 mol%,
[0202] Structural unit (AB) 1 mol% to 50 mol%,
[0203] Structural unit (AD) 7 mol% to 40 mol%.
[0204] Structural unit (AA) 50 mol% to 90 mol%,
[0205] Structural unit (AD) 10 mol% to 50 mol%,
[0206] Preferably
[0207] Structural unit (AA) 55 mol% to 80 mol%,
[0208] Structural unit (AD) 20 mol% to 45 mol%.
[0209] Structural unit (AA) 0.1 mol% to 90 mol%,
[0210] Structural unit (AB) 3 mol% to 89 mol%,
[0211] Structural unit (AC) 3 mol% to 49 mol%,
[0212] Structural unit (AD) 0.001 mol% to 47 mol%,
[0213] Preferably
[0214] Structural unit (AA) 6 mol% to 80 mol%,
[0215] Structural unit (AB) 5 mol% to 80 mol%,
[0216] The structural unit (AC) is 5 mol% to 44 mol%, the structural unit (AD) is 0.001 mol% to 40 mol%, and more preferably
[0217] Structural unit (AA) 16 mol% to 70 mol%, structural unit (AB) 7 mol% to 70 mol%, structural unit (AC) 7 mol% to 39 mol%, structural unit (AD) 0.001 mol% to 33 mol%. Structural unit (AA) 0.1 mol% to 90 mol%, structural unit (AB) 3 mol% to 90 mol%, structural unit (AC) 3 mol% to 50 mol%, structural unit (AE) 0.1 mol% to 90 mol%, preferably
[0218] The structural unit (AA) is 6 mol% to 80 mol%, the structural unit (AB) is 5 mol% to 80 mol%, the structural unit (AC) is 5 mol% to 45 mol%, the structural unit (AE) is 0.1 mol% to 80 mol%, and more preferably
[0219] Structural unit (AA) 16 mol% to 70 mol%, structural unit (AB) 7 mol% to 70 mol%, structural unit (AC) 7 mol% to 40 mol%, structural unit (AE) 0.1 mol% to 70 mol%. Structural unit (AA) 0.1 mol% to 80 mol%, structural unit (AD) 3 mol% to 50 mol%, structural unit (AE) 0.1 mol% to 80 mol%, preferably
[0220] The structural unit (AA) is 6 mol% to 70 mol%, the structural unit (AD) is 5 mol% to 45 mol%, and the structural unit (AE) is 1 mol% to 70 mol%.
[0221] The structural unit (AA) is 0.1 mol% to 90 mol%, the structural unit (AB) is 0.001 mol% to 85 mol%, the structural unit (AD) is 3 mol% to 50 mol%, the structural unit (AE) is 0.1 mol% to 95 mol%, and preferably
[0222] The structural unit (AA) is 6 mol% to 80 mol%, the structural unit (AB) is 0.001 mol% to 80 mol%, the structural unit (AD) is 5 mol% to 45 mol%, the structural unit (AE) is 0.1 mol% to 85 mol%, and more preferably
[0223] Structural unit (AA) 16 mol% to 70 mol%, structural unit (AB) 0.001 mol% to 70 mol%, structural unit (AD) 7 mol% to 40 mol%,
[0224] Structural unit (AE) 1 mol% to 70 mol%.
[0225] Structural unit (AA) 0.1 mol% to 90 mol%,
[0226] Structural unit (AC) 0.1 mol% to 47 mol%,
[0227] Structural unit (AD) 3 mol% to 49 mol%,
[0228] Structural unit (AE) 0.1 mol% to 90 mol%,
[0229] Preferably
[0230] Structural unit (AA) 6 mol% to 80 mol%,
[0231] Structural unit (AC) 1 mol% to 40 mol%,
[0232] Structural unit (AD) 5 mol% to 39 mol%,
[0233] Structural unit (AE) 0.1 mol% to 80 mol%.
[0234] Structural unit (AA) 0.1 mol% to 90 mol%,
[0235] Structural unit (AB) 3 mol% to 90 mol%,
[0236] Structural unit (AC) 3 mol% to 49 mol%,
[0237] Structural unit (AD) 0.001 mol% to 47 mol%,
[0238] Structural unit (AE) 0.1 mol% to 90 mol%,
[0239] Preferably
[0240] Structural unit (AA) 6 mol% to 80 mol%,
[0241] Structural unit (AB) 5 mol% to 80 mol%,
[0242] Structural unit (AC) 5 mol% to 44 mol%,
[0243] Structural unit (AD) 0.001 mol% to 40 mol%,
[0244] Structural unit (AE) 0.1 mol% to 80 mol%,
[0245] More preferably
[0246] Structural unit (AA) 16 mol% to 70 mol%,
[0247] Structural unit (AB) 7 mol% to 70 mol%,
[0248] Structural unit (AC) 7 mol% to 39 mol%,
[0249] Structural unit (AD) 0.001 mol% to 33 mol%,
[0250] Structural unit (AE) 0.1 mol% to 70 mol%.
[0251] Specific examples of the (meth)acrylic copolymer include copolymers in which the structural unit (AA) is a structural unit represented by the following general formula (A-1), the structural unit (AB) is a structural unit represented by the following general formula (A-2), the structural unit (AC) is a structural unit represented by the following general formula (A-3), and the structural unit (AE) is a structural unit represented by the following general formula (A-4).
[0252] [Chemistry 15]
[0253]
[0254] [Chemistry 16]
[0255]
[0256] [Chemistry 17]
[0257]
[0258] [Chemistry 18]
[0259]
[0260] In the general formulas (A-1) to (A-4), R 11 ~R 14 and R 19 represents a hydrogen atom or a methyl group. Among these, a methyl group is preferred.
[0261] R 15 ~R 18 and R 20 ~R21 It represents a hydrocarbon group having 1 to 10 carbon atoms which may have a cyclic structure or an aromatic ring, may have a substituent, may have an ether bond, and may have an unsaturated bond.
[0262] Examples of the hydrocarbon group having 1 to 10 carbon atoms include: divalent alkylene groups having a straight chain or branched chain, such as methylene, ethylene, propylene, butylene, pentylene, hexylene, heptylene, octylene, nonylene, and decylene; divalent hydrocarbon groups having an alicyclic structure, such as cyclohexylene, methylcyclohexylene, ethylcyclohexylene, dimethylcyclohexylene, diethylcyclohexylene, methylethylcyclohexylene, propylcyclohexylene, and methylpropylcyclohexylene; and divalent hydrocarbon groups having an aromatic structure, such as phenylene, methylphenylene, ethylphenylene, dimethylphenylene, methylethylphenylene, and naphthylene. Among these, methylene and ethylene are preferred, and R 15 ~R 16 More preferably, it is ethylene, R 17 ~R 18 More preferably, it is a methylene group. Examples of the substituent include a methyl group, a methoxy group, and the like.
[0263] m1 and m2 are 0 or 1, preferably 0. m3 and m4 are 0, 1 or 2, preferably 0.
[0264] R 22 R represents a hydrocarbon group having 1 to 30 carbon atoms which may have a cyclic structure or an aromatic ring, may have a substituent, may be alkylene oxide-modified, and may have one or two hetero atoms. 22 Preferably, it is a linear or branched alkyl group having 1 to 10 carbon atoms, an optionally substituted cycloalkyl group having 3 to 30 carbon atoms, or an optionally substituted aryl group having 6 to 30 carbon atoms.
[0265] Examples of alkyl groups having 1 to 10 carbon atoms include methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, and decyl. Examples of cycloalkyl groups having 3 to 30 carbon atoms include cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, norbornyl, dicyclopentyl, and adamantyl. Examples of the aryl group having 6 to 30 carbon atoms include phenyl, biphenyl, 1-naphthyl, 2-naphthyl, 9-anthryl, 9-phenanthryl, 1-pyrenyl, 5-naphthyl, 1-indenyl, 2-azulyl, 9-fluorenyl, terphenyl, quaterphenyl, o-tolyl, m-tolyl, and p-tolyl, xylyl, o-cumyl, m-cumyl, and p-cumyl, mesityl, pentalenyl, binaphthyl, trinaphthyl, quaternaryl, cycloheptatrienyl, biphenylene, dicyclopentadienylphenyl, fluoranthenyl, acenaphthyl, acetothrenyl, benzonaphthyl, anthracenyl, bianthryl, trianthryl, quaternaryl, anthraquinone, phenanthryl, triphenylene, pyrenyl, The substituents include methyl and ethyl, and more preferably methyl. In addition, examples of the substituents include methyl and methoxy.
[0266] X1 represents an epoxy acrylate residue, an ester bond, or a urethane bond having a secondary hydroxyl group. Among these, an ester bond and a urethane bond are preferred, and an ester bond is more preferred.
[0267] X2 and X3 independently represent an epoxy acrylate residue, an ester bond or a urethane bond having a secondary hydroxyl group. Among these, a urethane bond is preferred.
[0268] X1 to X3 are preferably different bonds or structures from each other.
[0269] U represents an ultraviolet absorbing group. The ultraviolet absorbing group may be any functional group having the structure exemplified as the ultraviolet absorbing group possessed by the structural unit (AA).
[0270] *Indicates the bonding site with other structural units.
[0271] (The molar ratio of the structural unit represented by the general formula (A-1)): (The molar ratio of the structural unit represented by the general formula (A-2)): (The molar ratio of the structural unit represented by the general formula (A-3)): (The molar ratio of the structural unit represented by the general formula (A-4)) is 0.1 to 89: 5 to 89: 5 to 50: 0.1 to 89. The preferred range of a: b: c: d can be set to the same range as the preferred range of the structural unit (AA), the structural unit (AB), the structural unit (AC) and the structural unit (AE).
[0272] Another specific example of the (meth)acrylic copolymer includes a copolymer in which the structural unit (AA) is a structural unit represented by the following general formula (A-5), the structural unit (AB) is a structural unit represented by the following general formula (A-6), the structural unit (AD) is a structural unit represented by the following general formula (A-7), and the structural unit (AE) is a structural unit represented by the following general formula (A-8).
[0273] [Chemistry 19]
[0274]
[0275] [Chemistry 20]
[0276]
[0277] [Chemistry 21]
[0278]
[0279] [Chemistry 22]
[0280]
[0281] In the general formulas (A-5) to (A-8), R 31 ~R 34 and R 39 and R and R independently represent a hydrogen atom or a methyl group. Among these, a methyl group is preferred.
[0282] R 35 ~R 38 Each independently represents a hydrocarbon group having 1 to 10 carbon atoms, which may have a cyclic structure or an aromatic ring, may have a substituent, may have an ether bond, and may have an unsaturated bond.
[0283] Examples of the hydrocarbon group having 1 to 10 carbon atoms include: divalent alkylene groups having a straight chain or branched chain, such as methylene, ethylene, propylene, butylene, pentylene, hexylene, heptylene, octylene, nonylene, and decylene; divalent hydrocarbon groups having an alicyclic structure, such as cyclohexylene, methylcyclohexylene, ethylcyclohexylene, dimethylcyclohexylene, diethylcyclohexylene, methylethylcyclohexylene, propylcyclohexylene, and methylpropylcyclohexylene; and divalent hydrocarbon groups having an aromatic structure, such as phenylene, methylphenylene, ethylphenylene, dimethylphenylene, methylethylphenylene, and naphthylene. Among these, methylene and ethylene are preferred, and R 35 ~R 36 More preferably, it is ethylene, R 37 ~R 38 More preferably, it is a methylene group. Examples of the substituent include a methyl group, a methoxy group, and the like.
[0284] m5 and m6 are 0 or 1, preferably 0.
[0285] R 40 R represents a hydrocarbon group having 1 to 10 carbon atoms, which may have a cyclic structure or an aromatic ring, may have a substituent, may have an ether bond, and may have an unsaturated bond. 40 Preferably, it is an alkylene group having 1 to 10 carbon atoms which may have a carboxyl group, a cycloalkylene group having 3 to 10 carbon atoms which may have a carboxyl group, a cycloalkene group having 3 to 10 carbon atoms which may have a carboxyl group, or an aryl group having 6 to 10 carbon atoms which may have a carboxyl group. 40 Specific examples include: R 35 ~R 38 Possible groups include hydrocarbon groups having 1 to 10 carbon atoms and cycloalkenyl groups having 3 to 10 carbon atoms, such as cyclopropenyl, cyclobutenyl, cyclopentenyl, cyclohexenyl, cycloheptenyl, and cyclooctenyl. Preferred groups include ethylene and propylene, and more preferred are ethylene.
[0286] R41 R represents a hydrocarbon group having 1 to 30 carbon atoms which may have a cyclic structure or an aromatic ring, may have a substituent, may be alkylene oxide-modified, and may have one or two hetero atoms. 41 Preferred is an alkyl group having 1 to 10 carbon atoms, an optionally substituted cycloalkyl group having 3 to 30 carbon atoms, or an optionally substituted aryl group having 6 to 30 carbon atoms.
[0287] Examples of alkyl groups having 1 to 10 carbon atoms include methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, and decyl. Examples of cycloalkyl groups having 3 to 30 carbon atoms include cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, norbornyl, dicyclopentyl, and adamantyl. Examples of the aryl group having 6 to 30 carbon atoms include phenyl, biphenyl, 1-naphthyl, 2-naphthyl, 9-anthryl, 9-phenanthryl, 1-pyrenyl, 5-naphthyl, 1-indenyl, 2-azulyl, 9-fluorenyl, terphenyl, quaterphenyl, o-tolyl, m-tolyl, and p-tolyl, xylyl, o-cumyl, m-cumyl, and p-cumyl, mesityl, pentalenyl, binaphthyl, trinaphthyl, quaternaryl, cycloheptatrienyl, biphenylene, dicyclopentadienylphenyl, fluoranthenyl, acenaphthyl, acetothrenyl, benzonaphthyl, anthracenyl, bianthryl, trianthryl, quaternaryl, anthraquinone, phenanthryl, triphenylene, pyrenyl, The substituents include methyl and ethyl, and more preferably methyl. In addition, examples of the substituents include methyl and methoxy.
[0288] X4 represents an epoxy acrylate residue, an ester bond, or a urethane bond having a secondary hydroxyl group, among which an ester bond is preferred.
[0289] U represents an ultraviolet absorbing group. The ultraviolet absorbing group may be any functional group having the structure exemplified as the ultraviolet absorbing group possessed by the structural unit (AA).
[0290] *Indicates the bonding site with other structural units.
[0291] (The molar ratio of the structural unit represented by the general formula (A-5)): (The molar ratio of the structural unit represented by the general formula (A-6)): (The molar ratio of the structural unit represented by the general formula (A-7)): (The molar ratio of the structural unit represented by the general formula (A-8)) is 0.1 to 90: 0.001 to 50: 5 to 50: 0.1 to 94. Among them, the preferred range of e: f: g: h can be set to the same range as the preferred range of the structural unit (AA), the structural unit (AB), the structural unit (AD) and the structural unit (AE).
[0292] The (meth)acrylic acid copolymer can be synthesized by appropriately combining the following monomers and copolymerizing them, and then grafting a UV absorbing group, a polymerizable unsaturated group, or a carboxyl group onto the side chain of the structural unit derived from the monomers (Ax1) to (Ax3).
[0293] (Aa) A monomer having a (meth)acryloyl group and an ultraviolet absorbing group
[0294] (Ac) a monomer having a (meth)acryloyl group and a carboxyl group
[0295] (Ae) A monomer having a (meth)acryloyl group and having neither an ultraviolet absorbing group nor a carboxyl group
[0296] (Ax1) a monomer having a (meth)acryloyl group and a hydroxyl group
[0297] (Ax2) a monomer having a (meth)acryloyl group and an isocyanate group
[0298] (Ax3) a monomer having a (meth)acryloyl group and a glycidyl group or an alicyclic epoxy group
[0299] The monomer (Aa) is a monomer for introducing an ultraviolet absorbing group into the (meth)acrylic copolymer.
[0300] In addition, from the viewpoint of improving the ultraviolet absorption capacity of the (meth)acrylic acid copolymer, the monomer (Aa) is preferably a monomer having a molar absorption coefficient of 3000 L / (mol·cm) or more at a wavelength of 355 nm. From the same viewpoint, the monomer (Aa) is more preferably a monomer having a molar absorption coefficient of 3000 L / (mol·cm) to 100000 L / (mol·cm) at a wavelength of 355 nm, further preferably a monomer having a molar absorption coefficient of 4000 L / (mol·cm) to 90000 L / (mol·cm), and particularly preferably a monomer having a molar absorption coefficient of 5000 L / (mol·cm) to 80000 L / (mol·cm). The molar absorption coefficient can be measured in the same manner as the molar absorption coefficient measurement conditions.
[0301] Examples of the monomer (Aa) include compounds described in JP-A-2004-182924, JP-A-2007-286123, JP-A-2007-331359, JP-A-2013-204001, JP-A-2015-124254, JP-A-2019-137844, and JP-A-2020-189906.
[0302] The monomer (Ac) is a monomer for introducing a carboxyl group into the (meth)acrylic acid copolymer. The monomer (Ac) is preferably a monomer without the ultraviolet absorbing group. In addition, the monomer (Ac) is preferably a monomer having a molar absorption coefficient of less than 3000 L / (mol·cm) at a wavelength of 355 nm. The molar absorption coefficient can be measured in the same manner as the molar absorption coefficient measurement conditions.
[0303] Examples of the monomer (Ac) include (meth)acrylic acid, mono(2-(meth)acryloyloxyethyl)succinate, (2-(meth)acryloyloxyethyl)hexahydrophthalate, (2-(meth)acryloyloxyethyl)phthalate, (2-(meth)acryloyloxyethyl)maleate, (2-(meth)acryloyloxyethyl)fumarate, (2-(meth)acryloyloxyethyl)itaconate, (2-(meth)acryloyloxyethyl)citraconate, carboxyethyl (meth)acrylate, 3-carboxypropyl (meth)acrylate, 4-carboxybutyl (meth)acrylate, mono-n-butyl (2-(meth)acryloyloxyethyl)maleate, mono-n-butyl (2-(meth)acryloyloxyethyl)fumarate, and mono-n-butyl (2-(meth)acryloyloxyethyl)itaconate.
[0304] The monomer (Ae) is a monomer for adjusting the molecular weight or the amount of functional groups of the (meth)acrylic copolymer.
[0305] Examples of the monomer (Ae) include ethyl (meth)acrylate, methyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, neopentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, propylene (meth)acrylate, butyl ... (meth)acrylates having an alkyl chain of 1 to 20 carbon atoms, preferably 1 to 10 carbon atoms, such as lauryl (meth)acrylate and stearyl (meth)acrylate, (meth)acrylates having an alkyl chain of 1 to 20 carbon atoms, preferably 1 to 10 carbon atoms, such as methoxyethyl (meth)acrylate, methoxytriethylene glycol (meth)acrylate, methoxydipropylene glycol (meth)acrylate, 2-ethylhexyl diglycol (meth)acrylate, butoxydiethylene glycol (meth)acrylate, (meth)acrylates having an alkyl chain of 1 to 10 carbon atoms modified by alkylene oxide, such as cyclohexyl (meth)acrylate, methylcyclohexyl (meth)acrylate, cyclododecyl (meth)acrylate, (meth)acrylate (meth)acrylates having an alicyclic hydrocarbon group having 3 to 30 carbon atoms, such as tert-butylcyclohexyl (meth)acrylate, cyclopentyl (meth)acrylate, dicyclopentyl (meth)acrylate, adamantane-1-yl (meth)acrylate, 4-tert-butylcyclohexyl (meth)acrylate, and 3,3,5-trimethylcyclohexyl (meth)acrylate; (meth)acrylates having an aromatic hydrocarbon group having 3 to 30 carbon atoms, such as benzyl (meth)acrylate, phenylethyl (meth)acrylate, phenoxyethyl (meth)acrylate, 2-biphenyl (meth)acrylate, and 2-naphthyl (meth)acrylate; and neopentyl (meth)acrylate. (meth)acrylates having an aromatic hydrocarbon group having 3 to 30 carbon atoms modified by alkylene oxide such as alcohol-acrylic acid-benzoate, phenoxyethylene glycol methacrylate, epoxidized-O-phenylphenol (meth)acrylate, phthalimide (meth)acrylate, maleimide (meth)acrylate, benzophenone (meth)acrylate, 2-hydroxy-4-(meth)acryloyloxybenzophenone, hydroxy-4-(2-(meth)acryloyloxy)ethoxybenzophenone, etc. having a hydrocarbon group having 1 to 30 carbon atoms which may have one or two hetero atoms.
[0306] The monomers (Ax1) to (Ax3) are monomers for introducing the functional groups into the side chains of the (meth)acrylic copolymer by grafting.
[0307] The monomers (Ax1) to (Ax3) are preferably monomers that do not have the ultraviolet absorbing group. In addition, the monomers (Ax1) to (Ax3) are preferably monomers whose molar absorption coefficient of the monomer (Aa) at a wavelength of 355 nm is less than 3000 L / (mol·cm). In addition, the monomers (Ax1) to (Ax3) are preferably monomers that do not have a carboxyl group. The molar absorption coefficient can be measured in the same manner as the molar absorption coefficient measurement conditions.
[0308] For example, the monomer (Ax1) having a hydroxyl group can be used to introduce a polymerizable unsaturated group into the (meth)acrylic copolymer via a urethane bond by reacting the hydroxyl group with a compound (Ay1a) having an isocyanate group and a polymerizable unsaturated group.
[0309] Alternatively, the monomer (Ax1) having a hydroxyl group may be used to introduce a carboxyl group into the (meth)acrylic acid copolymer via an ester bond by reacting the hydroxyl group with (Ay1b) dicarboxylic acid or its monoanhydride after copolymerization with other monomers.
[0310] Examples of such monomers (Ax1) include: 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, cyclohexanedimethanol mono(meth)acrylate, and ethyl-α-hydroxymethyl acrylate, etc.
[0311] Examples of the compound (Ay1a) having an isocyanate group and a polymerizable unsaturated group used together with the monomer (Ax1) include (2-(meth)acryloyloxyethyl)isocyanate and the like.
[0312] Examples of the (Ay1b) dicarboxylic acid or its monoanhydride used together with the monomer (Ax1) include chain hydrocarbon dicarboxylic acids, alicyclic hydrocarbon dicarboxylic acids, aromatic hydrocarbon dicarboxylic acids, and its monoanhydride.
[0313] Examples of the chain hydrocarbon dicarboxylic acids include succinic acid, acetylsuccinic acid, maleic acid, adipic acid, itaconic acid, azelaic acid, citramalic acid, malonic acid, glutaric acid, citric acid, tartaric acid, oxoglutaric acid, pimelic acid, sebacic acid, suberic acid, diglycolic acid, and dicarboxylic acids thereof into which any substituents are introduced.
[0314] Examples of the alicyclic hydrocarbon dicarboxylic acid include cyclobutane dicarboxylic acid, cyclopentane dicarboxylic acid, hexahydrophthalic acid, tetrahydrophthalic acid, methyltetrahydrophthalic acid, methylendomethylenetetrahydrophthalic acid, chlorendic acid, norbornane dicarboxylic acid, and dicarboxylic acids thereof into which any substituent is introduced.
[0315] Examples of the aromatic hydrocarbon dicarboxylic acid include phthalic acid, isophthalic acid, 1,8-naphthalene dicarboxylic acid, 2,3-naphthalene dicarboxylic acid, and the like, and these dicarboxylic acids into which any substituent is introduced.
[0316] The dicarboxylic acid is preferably succinic acid, itaconic acid, tetrahydrophthalic acid, and phthalic acid among these, and more preferably succinic acid, itaconic acid, and tetrahydrophthalic acid.
[0317] The dicarboxylic acid is preferably used in the form of a monoanhydride thereof.
[0318] Alternatively, a compound having an isocyanate group and an ultraviolet absorbing group, or a compound having an isocyanate group and a carboxyl group may be used instead of the compound having an isocyanate group and a polymerizable unsaturated group (Ay1a) to introduce an ultraviolet absorbing group or a carboxyl group into the side chain of the structural unit derived from the monomer (Ax1) via a urethane bond.
[0319] Alternatively, a compound having a carboxyl group and a UV absorbing group, or a compound having a carboxyl group and a polymerizable unsaturated group may be used instead of the dicarboxylic acid (Ay1b) or its monoanhydride to introduce a UV absorbing group or a polymerizable unsaturated group into the side chain of the structural unit derived from the monomer (Ax1) via a urethane bond.
[0320] In addition, the monomer (Ax2) having an isocyanate group can be used to react with the compound (Ay2) having a hydroxyl group and a polymerizable unsaturated group with the isocyanate group after copolymerization with other monomers, thereby introducing the polymerizable unsaturated group into the (meth)acrylic copolymer via a urethane bond.
[0321] Examples of such monomers (Ax2) include the compounds exemplified as the above-mentioned compounds having an isocyanate group and a polymerizable unsaturated group.
[0322] Examples of the compound (Ay2) having a hydroxyl group and a polymerizable unsaturated group used together with the monomer (Ax2) include the compounds exemplified as the monomer (Ax1).
[0323] In addition, a compound having a hydroxyl group and a UV absorbing group, or a compound having a hydroxyl group and a carboxyl group may be used instead of the compound having a hydroxyl group and a polymerizable unsaturated group (Ay2), and the UV absorbing group or the carboxyl group may be introduced into the side chain of the structural unit derived from the monomer (Ax2) via a carbamate bond.
[0324] In addition, a monomer (Ax3) having a glycidyl group or an alicyclic epoxy group can be used to react with other monomers to make a compound (Ay3) having a carboxyl group and a polymerizable unsaturated group react with the glycidyl group or the alicyclic epoxy group, thereby introducing a polymerizable unsaturated group into the (meth)acrylic copolymer via an epoxy acrylate residue.
[0325] Examples of such monomers (Ax3) include: glycidyl (meth)acrylate, β-propyl glycidyl (meth)acrylate, β-methylglycidyl-α-ethyl (meth)acrylate, 3-methyl-3,4-epoxybutyl (meth)acrylate, 4-methyl-4,5-epoxypentyl (meth)acrylate, 5-methyl-5,6-epoxyhexyl (meth)acrylate, and 3,4-epoxycyclohexylmethyl methacrylate, etc.
[0326] Examples of the compound (Ay3) having a carboxyl group and a polymerizable unsaturated group used together with the monomer (Ax3) include the compounds exemplified as the monomer (Ac).
[0327] Alternatively, the polyvalent carboxylic acid (Az3) or its anhydride may be further reacted with an epoxy acrylate residue generated from the monomer (Ax3) to introduce a carboxyl group into the (meth)acrylic acid copolymer via the epoxy acrylate residue.
[0328] Examples of the polycarboxylic acid to be reacted with the epoxy acrylate residue include the dicarboxylic acid or its monoanhydride, tricarboxylic acid or its monoanhydride, and tetracarboxylic acid or its dianhydride exemplified as the monomer (Ay1b).
[0329] Examples of the tricarboxylic acid include trimellitic acid and hexahydrotrimellitic acid.
[0330] Examples of the tetracarboxylic acid include chain hydrocarbon tetracarboxylic acids, alicyclic hydrocarbon tetracarboxylic acids, aromatic tetracarboxylic acids, and the like.
[0331] Examples of the chain hydrocarbon tetracarboxylic acid include butane tetracarboxylic acid, pentane tetracarboxylic acid, hexane tetracarboxylic acid, and chain hydrocarbon tetracarboxylic acids into which a substituent such as an alicyclic hydrocarbon group or an unsaturated hydrocarbon group is introduced.
[0332] Examples of the alicyclic hydrocarbon tetracarboxylic acid include cyclobutane tetracarboxylic acid, cyclopentane tetracarboxylic acid, cyclohexane tetracarboxylic acid, cycloheptane tetracarboxylic acid, norbornane tetracarboxylic acid, and alicyclic hydrocarbon tetracarboxylic acids into which a substituent such as a chain hydrocarbon group or an unsaturated hydrocarbon group is introduced.
[0333] Examples of the aromatic tetracarboxylic acid include pyromellitic acid, benzophenonetetracarboxylic acid, biphenyltetracarboxylic acid, diphenyl ether tetracarboxylic acid, diphenyl sulfone tetracarboxylic acid, naphthalene-1,4,5,8-tetracarboxylic acid, and naphthalene-2,3,6,7-tetracarboxylic acid.
[0334] The tetracarboxylic acid is preferably used in the form of its dianhydride.
[0335] For example, a copolymer having a structural unit (AA) represented by the general formula (A-1), a structural unit (AB) represented by the general formula (A-2), a structural unit (AC) represented by the general formula (A-3), and a structural unit (AE) represented by the general formula (A-4) can be synthesized by the following steps.
[0336] [Step (1)-1]
[0337] (Aa) a monomer having a (meth)acryloyl group and a UV absorbing group,
[0338] (Ac) a monomer having a (meth)acryloyl group and a carboxyl group,
[0339] (Ae) a monomer having a (meth)acryloyl group and having neither an ultraviolet absorbing group nor a carboxyl group, and
[0340] (Ax1) a monomer having a (meth)acryloyl group and a hydroxyl group
[0341] Process of obtaining copolymer by copolymerization
[0342] [Step (1)-2]
[0343] A step of reacting the copolymer obtained in step (1)-1 with a compound (Ay1a) having an isocyanate group and a polymerizable unsaturated group to form a urethane bond between the hydroxyl group derived from the monomer (Ax1) and the isocyanate group of the compound (Ay1a), thereby grafting the polymerizable unsaturated group to the copolymer;
[0344] The copolymerization in step (1)-1 can be carried out by mixing the copolymerizable monomers with a thermal polymerization initiator in a solvent and reacting them. The reaction temperature depends on the type of thermal polymerization initiator used, but for example, the reaction is preferably carried out in a solvent at a temperature range of 60°C to 100°C for 2 to 12 hours.
[0345] The thermal polymerization initiator may be a general thermal radical polymerization initiator, and is preferably an azo compound or a peroxide. From the viewpoint of forming a linear polymer, an azo compound is more preferred.
[0346] Examples of the azo compound include 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylbutyronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 1,1'-azobis(cyclohexane-1-carbonitrile), and 2,2'-azobis(isobutyric acid)dimethyl. Among them, 2,2'-azobis(2,4-dimethylvaleronitrile) is preferred from the viewpoint of reaction temperature.
[0347] The solvent can be appropriately selected from the solvents used in the resin composition. Examples of usable solvents include alcohols, glycols, aliphatic cyclic ketones, and acetates. Among these, it is preferred to use solvents other than alcohols.
[0348] Examples of glycols include ethylene glycol monomethyl ether acetate, ethylene glycol monoethyl ether acetate, ethylene glycol monopropyl ether acetate, ethylene glycol monobutyl ether acetate, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, propylene glycol monopropyl ether acetate, propylene glycol monobutyl ether acetate, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, ethylene glycol dipropyl ether, ethylene glycol dibutyl ether, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dipropyl ether, diethylene glycol dibutyl ether, propylene glycol dimethyl ether, propylene glycol diethyl ether, propylene glycol monomethyl ether, ethylene glycol monoethyl ether, and ethylene glycol monobutyl ether.
[0349] Examples of aliphatic cyclic ketones include cyclohexanone, o-methylcyclohexanone, m-methylcyclohexanone, and p-methylcyclohexanone.
[0350] Examples of acetates include ethyl acetate, n-propyl acetate, and n-butyl acetate.
[0351] In addition to these, saturated hydrocarbon solvents such as solvent naphtha, methyl ethyl ketone, methyl isobutyl ketone, n-octane, and isooctane, as well as ethyl cellosolve and butyl cellosolve may be used.
[0352] At this time, it is preferred not to use a solvent containing a hydroxyl group, such as isopropyl alcohol (IPA) or propylene glycol monomethyl ether (PGME). This can prevent the isocyanate group of the compound (Ay1a) having an isocyanate group and a polymerizable unsaturated group from reacting with the hydroxyl group of the solvent in the next step, thereby allowing the reaction of forming a urethane bond to proceed reliably and sufficiently.
[0353] The amount of the solvent is preferably 10 to 2000 parts by weight, more preferably 50 to 500 parts by weight, based on 100 parts by weight of the total amount of the copolymerized monomers mixed within the above range.
[0354] The reaction in step (1)-2 is preferably carried out by mixing a monomer (Ay1a) of a compound having an isocyanate group and a polymerizable unsaturated group with the reaction solution obtained in step (1)-1, and then reacting in a solvent at a temperature range of 40°C to 100°C for 2 to 12 hours.
[0355] The solvent can be appropriately selected from the above solvents for use. In addition, the reaction can be carried out by adding a catalyst as needed. Examples of the catalyst include: tin compounds or titanium compounds, and amine compounds, etc. Specific examples of the catalyst include: dibutyltin laurate, tetra-n-butoxytitanium, and triethylamine, etc. Among these, tin compounds are more preferred in terms of easy reaction control. The amount of catalyst added is preferably 0.01 to 10 parts by weight relative to a total of 100 parts by weight of the compound having an isocyanate group and a polymerizable unsaturated group in the monomer (Ay1a). At this time, it is preferred not to polymerize the (meth)acryloyl group of the compound having an isocyanate group and a polymerizable unsaturated group in the monomer (Ay1a), and a polymerization inhibitor, etc., may also be added for the above purpose.
[0356] The compound having an isocyanate group and a polymerizable unsaturated group in the monomer (Ay1a) is preferably reacted under the condition that the number of moles of the isocyanate group is less than the number of moles of the hydroxyl group derived from the monomer (Ax1). Specifically, the number of moles of the isocyanate group derived from the monomer (Ay1a) is more preferably 95% to 99% of the number of moles of the hydroxyl group derived from the monomer (Ax1).
[0357] Furthermore, the material used may be appropriately changed according to the structure of each structural unit of the obtained polymer.
[0358] In addition, a copolymer having a structural unit (AA) represented by the general formula (A-5), a structural unit (AB) represented by the general formula (A-6), a structural unit (AD) represented by the general formula (A-7), and a structural unit (AE) represented by the general formula (A-8) can be synthesized by the following steps.
[0359] [Step (2)-1]
[0360] (Aa) a monomer having a (meth)acryloyl group and a UV absorbing group,
[0361] (Ae) a monomer having a (meth)acryloyl group and having neither an ultraviolet absorbing group nor a carboxyl group, and
[0362] (Ax3) a monomer having a (meth)acryloyl group and a glycidyl group or an alicyclic epoxy group
[0363] Process of obtaining copolymer by copolymerization
[0364] [Step (2)-2]
[0365] A step of reacting the copolymer obtained in step (2)-1 with a compound (Ay3) having a carboxyl group and a polymerizable unsaturated group to form an epoxy acrylate residue by reacting a glycidyl group or an alicyclic epoxy group derived from the monomer (Ax3) with a carboxyl group of the compound (Ay3), thereby grafting a polymerizable unsaturated group onto the copolymer;
[0366] [Step (2)-3]
[0367] A step of reacting the copolymer to which the polymerizable unsaturated group is grafted in step (2)-2 with a polycarboxylic acid (Az3) or an anhydride thereof, and further grafting a carboxyl group to the copolymer by reacting a hydroxyl group derived from the monomer (Ax1) or an epoxy acrylate residue generated by the reaction of the monomer (Ax3) with the monomer (Ay3) with the carboxyl group or carboxylic acid anhydride group of the compound (Az3);
[0368] The copolymerization in step (2)-1 can be carried out in the same manner as the copolymerization in step (1)-1. The reaction temperature depends on the type of thermal polymerization initiator used, but the reaction is preferably carried out in a solvent at a temperature range of 60°C to 100°C for 2 to 12 hours.
[0369] The thermal polymerization initiator may be a general thermal radical polymerization initiator, and is preferably an azo compound or a peroxide. From the viewpoint of forming a linear polymer, an azo compound is more preferred.
[0370] Examples of the azo compound include 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylbutyronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 1,1'-azobis(cyclohexane-1-carbonitrile), and 2,2'-azobis(isobutyric acid)dimethyl. Among them, 2,2'-azobis(2,4-dimethylvaleronitrile) is preferred from the viewpoint of reaction temperature.
[0371] The solvent can be appropriately selected from the solvents used in the resin composition. Examples of usable solvents include alcohols, glycols, aliphatic cyclic ketones, and acetates. Among these, it is preferred to use solvents other than alcohols.
[0372] Examples of glycols include ethylene glycol monomethyl ether acetate, ethylene glycol monoethyl ether acetate, ethylene glycol monopropyl ether acetate, ethylene glycol monobutyl ether acetate, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, propylene glycol monopropyl ether acetate, propylene glycol monobutyl ether acetate, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, ethylene glycol dipropyl ether, ethylene glycol dibutyl ether, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dipropyl ether, diethylene glycol dibutyl ether, propylene glycol dimethyl ether, propylene glycol diethyl ether, propylene glycol monomethyl ether, ethylene glycol monoethyl ether, and ethylene glycol monobutyl ether.
[0373] Examples of aliphatic cyclic ketones include cyclohexanone, o-methylcyclohexanone, m-methylcyclohexanone, and p-methylcyclohexanone.
[0374] Examples of acetates include ethyl acetate, n-propyl acetate, and n-butyl acetate.
[0375] In addition to these, saturated hydrocarbon solvents such as solvent naphtha, methyl ethyl ketone, methyl isobutyl ketone, n-octane, and isooctane, as well as ethyl cellosolve and butyl cellosolve may be used.
[0376] At this time, by not using a solvent containing a hydroxyl group such as isopropyl alcohol (IPA) or propylene glycol monomethyl ether (PGME), the reaction between the anhydride group of the (Az3) polycarboxylic acid or its anhydride and the hydroxyl group of the solvent in the next step can be avoided, thereby reliably and fully performing the reaction of forming an ester bond.
[0377] The amount of the solvent is preferably 10 to 2000 parts by weight, more preferably 50 to 500 parts by weight, based on 100 parts by weight of the total amount of the copolymerized monomers mixed within the above range.
[0378] The reaction of step (2)-2 can be carried out in a solvent at a temperature range of 80°C to 130°C for 5 to 18 hours. In addition, the reaction can be efficiently carried out by adding a base catalyst. Examples of the base catalyst include ammonium salts such as tetraethylammonium bromide and triethylbenzylammonium chloride, and phosphines such as triphenylphosphine and tri(2,6-dimethoxyphenyl)phosphine.
[0379] The reaction of step (2)-3 can be carried out in a solvent at a reaction temperature in the range of 80°C to 130°C for 5 hours to 48 hours.
[0380] In addition, in step (2)-1, a monomer having a (meth)acryloyl group and a hydroxyl group (Ax1) is copolymerized, and in step (2)-3, an ester bond is simultaneously formed between the hydroxyl group derived from the monomer (Ax1) and the carboxyl group or carboxylic acid anhydride group of the compound (Az3), thereby grafting a carboxyl group to the copolymer. The reaction conditions in this case may be the same as those in step (2)-3.
[0381] Furthermore, the monomers and compounds exemplified in the above-mentioned synthesis methods are merely examples, and it is needless to say that monomers and compounds other than these having the same functional groups may also be used.
[0382] The content of the (meth) acrylic copolymer in the adhesive layer forming composition of the present embodiment is preferably 10% to 80% by mass, more preferably 30% to 80% by mass, and further preferably 50% to 80% by mass, relative to the total mass of the solid component. If the content of the (A) component is more than 10% by mass relative to the total mass of the solid component, it is easy to absorb the irradiated light (such as ultraviolet rays) and deteriorate, so the support can be easily separated from the adherend. In addition, if it is less than 80% by mass, the acidic group used to show alkali solubility can be fully consumed by the cross-linking reaction with the (B) component, so that alkali resistance can be improved.
[0383] 1-2. (B) Epoxy compounds having at least two epoxy groups
[0384] The adhesive layer-forming composition of the present embodiment contains 25% by mass to 70% by mass of the component (B) based on the total mass of the unsaturated group-containing alkali-soluble resin of the component (A).
[0385] By setting the (B) component to 25% by mass or more relative to the total mass of the (A) component, the alkali resistance can be sufficiently improved. In addition, by setting it to 70% by mass or less, the crosslinking density of the adhesive layer after hardening can be suppressed from becoming too high, and the toughness can be maintained, thereby improving the bonding strength.
[0386] In addition, component (B) preferably has an aromatic ring or an alicyclic structure, and more preferably has an aromatic ring structure. By having an aromatic ring or an alicyclic structure, the penetration of the alkaline stripping solution of the adhesive layer can be suppressed, thereby improving the alkali resistance. By having an aromatic ring, the alkali resistance can be further improved.
[0387] In addition, the absorbance of the component (B) at a wavelength of 266 nm is preferably 0.10 or more, more preferably 0.10 to 1.00, further preferably 0.20 to 1.00, and most preferably 0.25 to 1.00. By setting the absorbance of the component (B) at 266 nm to 0.10 or more, the processability (peelability) of the adhesive layer based on a 266 nm laser can be improved. In addition, by setting the absorbance of the component (B) at 266 nm to 1.00 or less, the adhesive layer can be prevented from becoming too hard, and both bonding strength and laser processability can be taken into account. The absorbance can be set to the following value, that is, the value obtained by measuring the absorbance of a 0.001 weight % concentration acetonitrile solution in a quartz cell with a light path length of 1 cm using an ultraviolet visible infrared spectrophotometer "UH4150" (manufactured by Hitachi High-Tech Sciences, Ltd.).
[0388] Examples of the component (B) include bisphenol A type epoxy compounds (e.g., jER 828: manufactured by Mitsubishi Chemical Co., Ltd., Shofree BATG: manufactured by Resonac Co., Ltd.), bisphenol F type epoxy compounds, bisphenol fluorene type epoxy compounds, phenol novolac type epoxy compounds, cresol novolac type epoxy compounds (e.g., EPPN-501H: manufactured by Nippon Kayaku Co., Ltd.), phenol aralkyl type epoxy compounds, phenol novolac compounds containing a naphthalene skeleton (e.g., NC-7000L: manufactured by Nippon Kayaku Co., Ltd.), biphenyl type epoxy compounds (e.g., jER YX4000: manufactured by Mitsubishi Chemical Co., Ltd.), naphthol aralkyl type epoxy compounds, trisphenol methane type epoxy compounds, tetraphenol ethane type epoxy compounds, glycidyl ethers of polyhydric alcohols (e.g., Epolight 100MF: manufactured by Kyoeisha Chemical Co., Ltd.), glycidyl esters of polycarboxylic acids, copolymers of monomers having (meth)acrylic acid groups containing glycidyl (meth)acrylate as units represented by copolymers of methacrylic acid and glycidyl methacrylate, 3',4'-epoxycyclohexylmethyl 3,4-epoxycyclohexanecarboxylate (e.g., Celloxide 2021P: manufactured by Daicel Co., Ltd.), butanetetracarboxylic acid tetra(3,4-epoxycyclohexylmethyl) modified ε -caprolactone (for example, EPOLEAD GT401: manufactured by Daicel Co., Ltd.), epoxy compounds having an epoxy cyclohexyl group represented by HiREM-1 manufactured by Shikoku Chemical Industry Co., Ltd., multifunctional epoxy compounds having a dicyclopentadiene skeleton (for example, HP7200 series: manufactured by DIC Corporation), 1,2-epoxy-4-(2-oxacyclopropyl)cyclohexane adduct of 2,2-bis(hydroxymethyl)-1-butanol (for example, EHPE3150: manufactured by Daicel Co., Ltd.), epoxidized polybutadiene (for example, NISSO-PB·JP-100: manufactured by Nippon Soda Co., Ltd.), epoxy compounds having a silicone skeleton, etc.
[0389] In the (B) component, an epoxy compound containing an alicyclic structure or an epoxy compound containing an aromatic ring structure is preferably used, and an epoxy compound containing an aromatic ring structure is more preferably used. By using such a (B) component, the solubility in the alkaline stripping solution during hardening is easily reduced, and the alkaline stripping solution resistance is easily improved. In addition, among the epoxy compounds containing aromatic ring structures, bisphenol A type epoxy compounds, bisphenol F type epoxy compounds, bisphenol fluorene type epoxy compounds, phenol novolac type epoxy compounds, cresol novolac type epoxy compounds, biphenyl type epoxy compounds, fluorene type epoxy compounds are preferably used, and biphenyl type epoxy compounds or fluorene type epoxy compounds are more preferably used. Biphenyl type epoxy compounds or fluorene type epoxy compounds have a structure after conjugating an aromatic ring, and the absorbance becomes higher. Therefore, biphenyl type epoxy compounds or fluorene type epoxy compounds can improve the laser stripping property of the adhesive layer.
[0390] The epoxy equivalent of the epoxy compound of component (B) is preferably 100 g / eq to 300 g / eq, and more preferably 100 g / eq to 250 g / eq. In addition, the number average molecular weight (Mn) of the epoxy compound of component (B) is preferably 100 to 5000. If the epoxy equivalent is 100 g / eq to 300 g / eq and the number average molecular weight (Mn) of the epoxy compound is 100 to 5000, a cured film with good solvent resistance can be obtained. In addition, if the epoxy equivalent is less than 300 g / eq, alkali resistance can be further improved. In addition, only one of these compounds can be used, or two or more can be used in combination.
[0391] Relative to the total mass of the (A) component, the content of the (B) component is 25% to 70% by mass, preferably 25% to 60% by mass, and more preferably 30% to 60% by mass. By setting it to 25% by mass or more, a sufficient cross-linked structure can be formed, so the alkali resistance can be further improved. In addition, if it is 70% by mass or less, there will be no unreacted (B) component remaining in the adhesive layer after hardening, and the toughness of the adhesive layer can be maintained, so the bonding strength can be improved.
[0392] The content of component (B) is preferably more than 0% by mass and less than 41% by mass, more preferably 3% to 41% by mass, and further preferably 15% to 41% by mass, relative to the total mass of the solid component. If the content of component (B) is 15% by mass or more relative to the total mass of the solid component, a sufficient cross-linked structure can be formed, thereby improving chemical resistance. In addition, if it is less than 41% by mass, unreacted component (B) will not remain in the cured adhesive layer, and toughness can be maintained, thereby improving bonding strength.
[0393] 1-3. (C) Polymerizable compound having at least one ethylenically unsaturated bond
[0394] (C) The polymerizable compound having at least one ethylenically unsaturated bond (hereinafter also referred to as "component (C)") improves the adhesive strength and solvent resistance of the cured film formed by curing the curable composition to the adherend. The component (C) may have one or more polymerizable unsaturated groups that can react (polymerize) with the polymerizable unsaturated groups of the component (A) or other polymerizable unsaturated groups of the molecules of the component (C).
[0395] From the viewpoint of improving the bonding strength, the component (C) is preferably a liquid at 25° C. If the component (C) is a liquid at 25° C., the liquid property of the coating film of the adhesive layer-forming composition is improved. As a result, when the support and the adherend are bonded via the adhesive layer, the followability of the coating film to the support and the adherend is improved, thereby improving the bonding strength.
[0396] Relative to the total mass of (A) component and (B) component, the content of (C) component is preferably 1% to 20% by mass, more preferably 1% to 10% by mass, and further preferably 1% to 5% by mass. If the content of (C) component is more than 1% by mass relative to the total mass of (A) component and (B) component, the liquid property of the coating film of the adhesive layer forming composition can be improved. Thus, when the support and the adherend are adhered via the adhesive layer, the followability of the coating film to the support and the adherend is improved, thereby improving the bonding strength. If it is less than 20% by mass, the excessive increase of the cross-linked structure with high flexibility can be suppressed, thereby improving alkali resistance. In addition, due to the relative increase in the content of (A) component and (B) component with high laser absorptivity, laser processability can also be improved. If it is less than 10% by mass, alkali resistance and laser processability can be further improved.
[0397] Relative to the mass of (A) component, the content of (C) component is preferably 1% to 25% by mass, more preferably 1% to 13% by mass, and further preferably 1% to 7% by mass. If the content of (C) component is more than 1% by mass relative to the mass of (A) component, the liquid property of the coating film of the adhesive layer forming composition can be improved. Thus, when the support and the adherend are adhered via the adhesive layer, the followability of the coating film to the support and the adherend is improved, thereby improving the bonding strength. If it is less than 25% by mass, the excessive increase of the cross-linked structure with high flexibility can be suppressed, thereby improving alkali resistance.
[0398] The polymerizable unsaturated group is preferably a functional group identical to the polymerizable unsaturated group possessed by the (A) component. Specifically, the polymerizable unsaturated group is preferably a (meth)acryloyl group. In addition, the (C) component may be a monomer, an oligomer, or a polymer. The (C) component is preferably a monomer or an oligomer.
[0399] Examples of the component (C) include (meth)acrylates such as ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, tetramethylene glycol di(meth)acrylate, glycerol di(meth)acrylate, glycerol tri(meth)acrylate, sorbitol penta(meth)acrylate, sorbitol hexa(meth)acrylate, trimethylolpropane tri(meth)acrylate, trimethylolethane tri(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, and dipentaerythritol hexa(meth)acrylate, or quaternary acrylates such as ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, and dipropylene glycol di(meth)acrylate. Urethane acrylate monomers such as pentaerythritol triacrylate toluene diisocyanate urethane prepolymer, pentaerythritol triacrylate hexamethylene isocyanate urethane prepolymer, pentaerythritol triacrylate isophorone diisocyanate urethane prepolymer, and dipentaerythritol pentaacrylate hexamethylene diisocyanate urethane prepolymer; or epoxy (meth) acrylates such as bisphenol A type epoxy (meth) acrylate, bisphenol F type epoxy (meth) acrylate, bisphenol fluorene type epoxy (meth) acrylate, diphenylfluorene type epoxy (meth) acrylate, phenol novolac type epoxy (meth) acrylate, cresol novolac type epoxy (meth) acrylate, and phenol aralkyl type epoxy (meth) acrylate; or dendrimers having a (meth) acryloyl group, etc.
[0400] The component (C) preferably has two or more (meth)acryloyl groups, and more preferably has three or more (meth)acryloyl groups. When the component (C) has two or more (meth)acryloyl groups, the crosslinking density is increased, and the solvent resistance of the coating film or cured film is improved.
[0401] The acrylic acid equivalent of component (C) is preferably 50g / eq to 500g / eq, more preferably 70g / eq to 400g / eq, and further preferably 70g / eq to 300g / eq. If the acrylic acid equivalent of the polymerizable compound is less than 500g / eq, the sensitivity to radiation (such as ultraviolet rays) is high. In addition, since the crosslinking density is increased, the alkali resistance can be improved. If the acrylic acid equivalent is less than 400g / eq, the alkali resistance can be further improved, and if the acrylic acid equivalent is less than 300g / eq, the alkali resistance can be further improved. If the acrylic acid equivalent is more than 50g / eq, the crosslinking density will not become too high, and the laser stripping property will become better. In addition, the acrylic acid equivalent of the polymerizable compound can be obtained, for example, by dividing the molecular weight by the number of acrylic acid functional groups. In addition, the weight average molecular weight (Mw) of the polymerizable compound can be obtained, for example, using the gel permeation chromatography (GPC) "HLC-8220GPC".
[0402] From the viewpoint of further improving the adhesion of the cured film to the adherend, the (C) component may include an alkylene oxide-modified or lactone-modified compound. As the (C) component, when using an alkylene oxide-modified or lactone-modified compound, relative to the total mass of the (A) component and the (B) component, preferably 1% by mass to 15% by mass, more preferably 1% by mass to 10% by mass, and further preferably 1% by mass to 5% by mass. If the content of the (C) component is more than 1% by mass relative to the total mass of the (A) component and the (B) component, the liquid property of the coating film of the adhesive layer forming composition will be improved. Thus, when the support and the adherend are attached via the adhesive layer, the followability of the coating film to the support and the adherend is improved, thereby improving the bonding strength. If it is less than 15% by mass, the excessive increase of the cross-linked structure with high flexibility can be suppressed, thereby improving alkali resistance.
[0403] As component (C), a compound modified by alkylene oxide or lactone and a compound not containing alkylene oxide modified sites and lactone modified sites may also be used in combination. In this case, from the viewpoint of increasing crosslinking density to improve alkali resistance, the content of the compound not containing alkylene oxide modified sites and lactone modified sites is preferably 75% by mass to 100% by mass, more preferably 85% by mass to 100% by mass, and further preferably 95% by mass to 100% by mass, relative to the total mass of component (C).
[0404] The alkylene oxide-modified product is preferably a compound having an alkylene oxide group having 2 to 6 carbon atoms, more preferably a compound having an alkylene oxide group having 2 to 4 carbon atoms, and still more preferably a compound having an alkylene oxide group having 2 to 3 carbon atoms.
[0405] The alkylene oxide modification is preferably a compound to which 1 to 15 moles of alkylene oxide are added, for example, relative to 1 mole of the compound having multiple polymerizable unsaturated groups as shown in the example of the (C) component, more preferably a compound to which 2 to 10 moles of alkylene oxide are added, and most preferably a compound to which 2 to 8 moles of alkylene oxide are added. By adding more than 1 mole of alkylene oxide, the fluidity of the curable composition can be increased to provide good bonding strength. In addition, by setting it to less than 15 moles, the crosslinking density can be appropriately reduced while maintaining the bonding strength, so that good laser stripping can be provided, and further by setting it to less than 10 moles, better laser stripping can be provided.
[0406] The lactone modified product preferably has a structure in which a lactone having 2 to 6 carbon atoms is ring-opened (-C(=O)-(CH2) k -O-, k is a number less than the number of carbon atoms of the lactone by 1), more preferably a compound having a structure in which a lactone having 4 to 6 carbon atoms is ring-opened, and still more preferably a compound having a structure in which a lactone having 6 carbon atoms is ring-opened.
[0407] The lactone modified product is preferably a compound to which 1 to 15 mol of lactone is added, more preferably 2 to 10 mol of lactone is added, and most preferably 2 to 8 mol of lactone is added, for example, to 1 mol of the compound having multiple polymerizable unsaturated groups shown as an example of the component (C). The reason for the preferred range is the same as the reason for the preferred alkylene oxide modified product.
[0408] The modified product may be, for example, a compound represented by the following general formula (C-1).
[0409] [Chemistry 23]
[0410]
[0411] In formula (C-1), V is independently an alkylene oxide group or a group having a structure in which a lactone is ring-opened. a to e are independently integers of 0 to 6, wherein at least one of a to e is an integer of 1 to 6. a to e are preferably 1 or 2. R 51 ~R 55 Preferably, each of R 51 ~R 55 At least two of them are (meth)acryloyl groups. 51 ~R 55 Preferably, all of them are (meth)acryloyl groups. T is a group selected from the group consisting of substituted or unsubstituted monovalent to tetravalent hydrocarbon groups, -O- and -S-, preferably a substituted or unsubstituted divalent hydrocarbon group, -O- and -S-, more preferably -O-. q is independently 0 or 1, preferably 0. r is an integer of 1 to 4, preferably 2.
[0412] Examples of the modified products represented by the general formula (C-1) include: ethylene oxide-modified dipentaerythritol hexaacrylate, dipentaerythritol dicaprolactone hexaacrylate, dipentaerythritol tricaprolactone hexaacrylate, dipentaerythritol hexacaprolactone hexaacrylate, dipentaerythritol polycaprolactone hexaacrylate (all manufactured by Nippon Kayaku Co., Ltd.), trimethylolpropane propylene oxide-modified triacrylate, and trimethylolpropane ethylene oxide-modified triacrylate (all manufactured by Toagosei Co., Ltd.).
[0413] Examples of the modified products other than the compound represented by the general formula (C-1) include bisphenol F ethylene oxide-modified diacrylate, bisphenol A ethylene oxide-modified diacrylate, isocyanuric acid ethylene oxide-modified diacrylate and isocyanuric acid ethylene oxide-modified triacrylate, diglycerol ethylene oxide-modified acrylate (all manufactured by Toagosei Co., Ltd.), and phosphazene ethylene oxide-modified hexa(meth)acrylate.
[0414] 1-4. (D) Solvent
[0415] (D) component includes: alcohols such as methanol, ethanol, n-propanol, isopropanol, ethylene glycol, propylene glycol, 3-methoxy-1-butanol, ethylene glycol monobutyl ether, 3-hydroxy-2-butanone, diacetone alcohol; terpenes such as α-terpineol and β-terpineol; ketones such as acetone, methyl ethyl ketone, cyclohexanone, methyl isobutyl ketone, cyclopentanone, N-methyl-2-pyrrolidone; aromatic hydrocarbons such as toluene, xylene, tetramethylbenzene; cellosolve, methyl cellosolve, ethyl cellosolve, carbitol, methyl carbitol, ethyl carbitol, butyl carbitol, diethylene glycol ethyl methyl ether , propylene glycol monomethyl ether, propylene glycol monoethyl ether, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, triethylene glycol monomethyl ether, triethylene glycol monoethyl ether and other glycol ethers; ethyl acetate, butyl acetate, ethyl lactate, 3-methoxybutyl acetate, 3-methoxy-3-butyl acetate, 3-methoxy-3-methyl-1-butyl acetate, cellosolve acetate, ethyl cellosolve acetate, butyl cellosolve acetate, carbitol acetate, ethyl carbitol acetate, butyl carbitol acetate, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate and other esters. By using these to dissolve and mix, a uniform solution composition can be prepared. The amount of solvent varies depending on the target viscosity, but in terms of imparting appropriate coating adaptability, it is preferably 50% to 90% by mass of the total mass of the adhesive layer forming composition.
[0416] These solvents may be used alone or in combination of two or more in order to have necessary properties such as coating properties. However, in order to dissolve a large amount of component (B) in a short time, it is preferred to include a ketone solvent, more preferably acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclopentanone, and cyclohexanone, and further preferably cyclohexanone.
[0417] The content of the ketone solvent is preferably 10% to 80% by mass of the total mass of the component (D), and more preferably 20% to 70% by mass. If it is 10% by mass or more, the component (B) can be easily dissolved, and if it is 80% by mass or less, the residual solvent in the coating / drying process can be suppressed. In addition, the preferred content when using cyclohexanone as the ketone solvent is also in the same range as described above.
[0418] The content of the ketone solvent is preferably 5% to 72% by mass of the total mass of the adhesive layer forming composition, and more preferably 10% to 63% by mass. If it is 5% by mass or more, the (B) component can be easily dissolved, and if it is 72% by mass or less, the residual solvent in the coating / drying process can be suppressed. In addition, the preferred content when using cyclohexanone as the ketone solvent is also in the same range as described above.
[0419] 1-5. Other additives
[0420] The adhesive layer forming composition of the present embodiment may contain additives such as a photopolymerization initiator, a photosensitizer, a curing agent, a curing accelerator, a thermal polymerization inhibitor, an antioxidant, a plasticizer, a filler, a leveling agent, a defoaming agent, a surfactant, and a coupling agent as needed. In addition, an ultraviolet absorber or a pigment for improving the absorptivity of the irradiated light may also be contained.
[0421] 1-5-1. Photopolymerization initiator
[0422] The photopolymerization initiator is a compound that generates active species such as radicals, cations, and anions by light stimulation, and initiates a polymerization reaction. A photopolymerization initiator that generates radicals by light irradiation is preferred.
[0423] When exposure and development are performed to form a pattern on the adhesive layer, it is preferred that a photopolymerization initiator be included in the adhesive layer-forming composition. The polymerizable unsaturated groups of component (A) or component (C) react with each other through the active species generated by the photopolymerization initiator. As a result, a difference in solubility in an alkaline developer or the like occurs between the exposed portion and the unexposed portion, and patterning of the adhesive layer can be performed.
[0424] Examples of the photopolymerization initiator include oxime ester initiators, α-hydroxyacetophenone initiators, α-aminoacetophenone initiators, acylphosphine oxide initiators, and intramolecular hydrogen abstraction photopolymerization initiators. Among them, from the viewpoint of shortening the curing time of the curable composition, oxime ester initiators or α-aminoacetophenone initiators are preferred, and α-aminoacetophenone initiators are more preferred. Commercially available photopolymerization initiators can be used.
[0425] Examples of the photopolymerization initiator include polymerization initiators described in paragraphs 0031 to 0042 of JP-A-2011-095716 and polymerization initiators described in paragraphs 0064 to 0081 of JP-A-2015-014783.
[0426] Examples of the α-aminoacetophenone-based initiator include 2-(dimethylamino)-2-[(4-methylphenyl)methyl]-1-[4-(4-morpholinyl)phenyl]-1-butanone (trade name: Omnirad 379EG, Omnirad series are products of IGM Resins BV), 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropane-1-one (trade name: Omnirad 907), and APi-307 (1-(biphenyl-4-yl)-2-methyl-2-morpholinopropane-1-one, manufactured by Shenzhen UV-ChemTech Ltd.).
[0427] Examples of the oxime ester initiator include O-oxime ester photopolymerization initiators represented by the general formula (E-1) or the general formula (E-2).
[0428] [Chemistry 24]
[0429]
[0430] In formula (E-1), R 61 , R 62 Each independently represents an alkyl group having 1 to 15 carbon atoms, an aryl group having 6 to 18 carbon atoms, an arylalkyl group having 7 to 20 carbon atoms, or a heterocyclic group having 4 to 12 carbon atoms, and R 63 represents an alkyl group having 1 to 15 carbon atoms, an aryl group having 6 to 18 carbon atoms, or an arylalkyl group having 7 to 20 carbon atoms. Here, the alkyl group and the aryl group may be substituted by an alkyl group having 1 to 10 carbon atoms, an alkoxy group having 1 to 10 carbon atoms, an alkanoyl group having 1 to 10 carbon atoms, or a halogen, and the alkylene moiety may contain an unsaturated bond, an ether bond, a thioether bond, or an ester bond. In addition, the alkyl group may be any of a linear, branched, or cyclic alkyl group.
[0431] [Chemistry 25]
[0432]
[0433] In formula (E-2), R 64 and R 65 Each of R is independently a linear or branched alkyl group having 1 to 10 carbon atoms, a cycloalkyl group, a cycloalkylalkyl group or an alkylcycloalkyl group having 4 to 10 carbon atoms, or a phenyl group which may be substituted by an alkyl group having 1 to 6 carbon atoms. 66 Each independently represents a linear or branched alkyl or alkenyl group having 2 to 10 carbon atoms, and a portion of the -CH2- group in the alkyl or alkenyl group may be substituted with an -O- group. 64 ~R 66 A part of the hydrogen atoms in the group may be substituted by halogen atoms.
[0434] Examples of commercially available oxime ester initiators include 1,2-octanedione, 1-[4-(phenylthio)phenyl-, 2-(O-benzoyl oxime)] (trade name: IRGACURE OXE-01, IRGACURE series manufactured by BASF), ethyl ketone, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]-, 1-(O-acetyl oxime) (trade name: IRGACURE OXE-02, manufactured by BASF), 8-[5-(2,4,6-trimethylphenyl)- [(2- ... Japan), 1-[4-(phenylthio)phenyl]-3-cyclopentylpropane-1,2-dione-2-(O-benzoyl oxime) (trade name: TR-PBG-305, manufactured by Changzhou Qiangli Electronic New Materials Co., Ltd.), 1,2-propanedione, 3-cyclohexyl-1-[9-ethyl-6-(2-furanylcarbonyl)-9H-carbazole-3-yl]-, 2-(O-acetyl oxime) (trade name: TR-PBG-326, manufactured by Changzhou Qiangli Electronic New Materials Co., Ltd.), and 3-cyclohexyl-1-(6-(2-(benzoyloxyimino)hexanoyl)-9-ethyl-9H-carbazole-3-yl)-propane-1,2-dione-2-(O-benzoyl oxime) (trade name: TR-PBG-391, manufactured by Changzhou Qiangli Electronic New Materials Co., Ltd.).
[0435] Examples of other photopolymerization initiators include 2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]phenyl}-2-methyl-propane-1-one (trade name: Omnirad 127), 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone-1 (trade name: Omnirad 369), 2-hydroxy-2-methyl-1-phenyl-propane-1-one (trade name: Omnirad 500), and 2-hydroxy-2-methyl-1-phenyl-propane-1-one. )1173), 1-hydroxy-cyclohexyl-phenyl-ketone (trade name: Omnirad 184), 2,2-dimethoxy-1,2-diphenylethane-1-one (trade name: Omnirad 651), 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (trade name: Omnirad TPOH), and bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (trade name: Omnirad 819).
[0436] In the adhesive layer forming composition, the content of the photopolymerization initiator is preferably 0.1% to 30% by mass, more preferably 0.3% to 20% by mass, relative to the total mass of component (A). If the content of the photopolymerization initiator is 0.1% by mass or more, photopolymerization can be promoted, thereby accelerating the speed of photopolymerization. In addition, if the content of the photopolymerization initiator is 30% by mass or less, excessive sensitivity can be suppressed, and it is not easy to produce scorching, peeling impurities, etc. when irradiating light for ablation.
[0437] 1-5-2. Photosensitizer
[0438] Examples of the photosensitizer include: acetophenones such as triethanolamine, triisopropanolamine, benzophenone, 4,4'-bisdimethylaminobenzophenone (Michler's ketone), 4-phenylbenzophenone, 4,4'-dichlorobenzophenone, hydroxybenzophenone, 4,4'-diethylaminobenzophenone, acetophenone, 2,2-diethoxyacetophenone, p-dimethylacetophenone, p-dimethylaminoacetophenone, dichloroacetophenone, trichloroacetophenone, and p-tert-butylacetophenone; benzoin ethers such as benzoin, benzoin methyl ether, benzoin isopropyl ether, and benzoin isobutyl ether; 2-dimethylaminoethylbenzoic acid, 4-dimethylaminobenzoic acid ethyl ester, 4-dimethylaminobenzoic acid (n-butyloxy) ethyl ester, 4-dimethylaminobenzoic acid isopentyl ester, 4-dimethylaminobenzoic acid 2 Benzophenone series such as 2-ethylhexyl ester, 2,4-diethylthioxanthone, 2,4-diisopropylthioxanthone, 4-benzoyl-4'-methyl-diphenyl sulfide, acrylated benzophenone, 3,3',4,4'-tetra(tert-butylperoxycarbonyl)benzophenone, and 3,3'-dimethyl-4-methoxybenzophenone; thioxanthone series such as 2-isopropylthioxanthone, 2,4-dimethylthioxanthone, 2,4-diethylthioxanthone, and 2,4-dichlorothioxanthone; aminobenzophenone series such as 4,4'-bisdiethylaminobenzophenone; 10-butyl-2-chloroacridone, 2-ethylanthraquinone, 9,10-phenanthrenequinone, and camphorquinone.
[0439] In the curable composition, the content of the photosensitizer is preferably 0.5 mass % to 400 mass %, more preferably 1 mass % to 300 mass % relative to the total mass of the photopolymerization initiator. If the content of the photosensitizer is 0.5 mass % or more, the sensitivity of the photopolymerization initiator can be increased, thereby accelerating the speed of photopolymerization. In addition, if the content of the photosensitizer is 400 mass % or less, excessive increase in sensitivity can be suppressed, and it is not easy to generate burning, peeling impurities, etc. when irradiating light for ablation.
[0440] 1-5-3. Others
[0441] Examples of hardeners include: amine compounds, polycarboxylic acid compounds, phenol resins, amino resins, dicyandiamide, Lewis acid complexes, etc. that help harden epoxy resins. Examples of hardening accelerators include: tertiary amines, quaternary ammonium salts, tertiary phosphines, quaternary phosphonium salts, borates, Lewis acids, organometallic compounds, imidazoles, etc. that help harden epoxy resins. Examples of thermal polymerization inhibitors and antioxidants include: hydroquinone, hydroquinone monomethyl ether, pyrogallol, tert-butylcatechol, phenothiazine, hindered phenol compounds, etc. Examples of plasticizers include: dibutyl phthalate, dioctyl phthalate, tricresyl phosphate, etc. Examples of fillers include: glass fiber, silica, mica, alumina, etc. Examples of defoamers or leveling agents include: silicone, fluorine, and acrylic compounds. Examples of surfactants include fluorine surfactants, silicone surfactants, etc. Examples of the coupling agent include 3-(glycidyloxy)propyltrimethoxysilane, 3-acryloxypropyltrimethoxysilane, 3-isocyanatopropyltriethoxysilane, 3-ureidopropyltriethoxysilane, and the like.
[0442] 2. Laminated body
[0443] The laminated body of the present embodiment includes a support, an adherend, and an adhesive layer, wherein the adhesive layer is disposed between the support and the adherend and includes a coating film or a cured film of the adhesive layer-forming composition.
[0444] The laminated body of the present embodiment can also be suitably used as a substrate used in patterning using a resist material, and a resist layer or a material layer may be disposed on the surface of an adherend opposite to the surface in contact with the adhesive layer.
[0445] Here, the material layer is not particularly limited if it is a layer that can be patterned using a resist material. The material layer includes a metal film or a semiconductor film used in a semiconductor element, wiring, terminal, etc. contained in an electronic device. The material layer may be a patterned layer or an unpatterned layer. When the material layer includes two or more layers, it may be a layer in which all layers are unpatterned, a layer in which a portion is patterned and the rest is unpatterned, or a layer in which all layers are patterned.
[0446] For example, in the case where the material layer is patterned by an etching process, the resist layer may also be configured to sandwich the material layer between the resist layer and the adherend. In this case, the material layer preferably includes an unpatterned layer, and in the case where the material layer includes two or more layers, it is preferred that at least one layer is an unpatterned layer. In the case where a concave-convex pattern is simply formed on the substrate, or in the case where the material layer is patterned by a lift-off process, the resist layer may also be configured to be in contact with the adherend.
[0447] In addition, the laminate of this embodiment may also include a material layer, which is arranged on the opposite side of the surface of the adherend where the adhesive layer is arranged and is patterned. When the material layer includes two or more layers, as long as at least one layer is patterned, it may also include an unpatterned layer.
[0448] 2-1. Support
[0449] The type of the support is not limited as long as an adhesive layer can be formed on the surface thereof.
[0450] In this embodiment, the support body preferably has laser transmittance. In particular, the support body is more preferably transparent to light (laser) with a wavelength of 10nm to 400nm, and more preferably transparent to light (laser) with a wavelength of 100nm to 400nm. Examples of the support body with the laser transmittance include: glass substrates, acrylic substrates, sapphire substrates, quartz substrates, etc. Among them, regarding glass substrates and acrylic substrates, it is necessary to use the following substrates: the composition of the substrate makes the transmittance of the wavelength of the light used sufficient. Among the support bodies, glass substrates are preferred.
[0451] 2-2. Adherent
[0452] The example of adherend comprises: semiconductor wafer, semiconductor chip, light emitting element, optical glass wafer, metal foil, grinding pad, resin coating, wiring layer etc.Adherend can be single layer, also can have more than two layers of multilayer structure, part or all layers can be patterned.In the case of used substrate in the patterning using resist material, adherend preferably comprises semiconductor wafer.
[0453] In addition, the adherend may have a concavo-convex pattern formed on the surface opposite to the surface in contact with the adhesive layer.
[0454] 2-3. Adhesive layer
[0455] The adhesive layer is formed by applying the adhesive layer-forming composition to the surface of the support and / or the adherend and at least drying the solvent.
[0456] In the adhesive layer that has undergone the solvent drying step, the substance before being heat-treated under the preferred heat-treatment conditions (temperature, time) for causing a cross-linking reaction described later is also referred to as the "coating film" of the adhesive layer-forming composition. In addition, the substance after being heat-treated under the preferred heat-treatment conditions (temperature, time) for causing a cross-linking reaction described later is also referred to as the "cured film" of the adhesive layer-forming composition.
[0457] 2-4. Resist layer
[0458] As the component used in the resist layer, known materials can be used. The component used in the resist layer is not particularly limited as long as it can be patterned in the developing step described later and can be stripped in the stripping step. The resist layer can be a positive resist layer or a negative resist layer.
[0459] As the resist layer formation product, a commercially available liquid resist layer formation product or dry film resist may be used.
[0460] 2-5. Material layer
[0461] The material layer may be a single layer or may have a multi-layer structure of two or more layers.
[0462] As the material used for the material layer, a known material can be used. Examples of the material used for the material layer include silicon materials such as silicon oxide, silicon nitride, and silicon oxynitride, or metal materials such as metal oxide.
[0463] 3. Method for manufacturing laminate
[0464] The method for producing a laminate of the present embodiment includes: i) forming an adhesive layer containing the adhesive layer-forming composition on the surface of one or both of a support and an adherend; and ii) bonding the support and the adherend via the formed adhesive layer.
[0465] Furthermore, the method for producing a laminate may include a step of exposing and developing the adhesive layer, or a step of providing a resist layer.
[0466] Preferably, the adhesive layer is subjected to heat treatment in the step of i) forming the adhesive layer and / or the step of ii) bonding the support and the adherend. By heating the adhesive layer, the polymerizable unsaturated groups of the component (A) or the component (C) react with each other, and then the acidic group of the component (A) reacts with the epoxy group of the component (B). By the reaction, a strong cross-linked structure can be formed, thereby further improving the alkali resistance of the adhesive layer.
[0467] The heat treatment can be performed before the step requiring alkali resistance, and is not limited to the step i) forming the adhesive layer or the step ii) bonding the support and the adherend. For example, in the case of a laminate including a resist layer, the heat treatment can be performed before the stripping step of stripping the resist layer using an alkaline stripping solution described later.
[0468] The heating treatment temperature for carrying out the cross-linking reaction is preferably 150°C to 250°C, and more preferably 180°C to 230°C. In addition, the heating treatment time is preferably 10 minutes to 120 minutes, and more preferably 30 minutes to 90 minutes. By setting the treatment temperature to above 150°C and the treatment time to above 10 minutes, the cross-linking reaction is carried out well, thereby improving the alkali resistance of the adhesive layer. By setting the treatment temperature to below 250°C and the treatment time to below 120 minutes, unexpected side reactions will not occur, thereby suppressing the coloring of the cured film or the reduction in the bonding strength.
[0469] Hereinafter, each step will be described.
[0470] 3-1. Step of forming adhesive layer
[0471] The adhesive layer forming step is a step of applying the adhesive layer forming composition to the surface of a support and / or an adherend to form an adhesive layer containing the adhesive layer forming composition.
[0472] Examples of the method for applying the adhesive layer-forming composition include known solution dipping method, spin coating method, ink jet method, spray method, and method using a roll coater, land coater, slit coater or spinner.
[0473] After the adhesive layer is imparted by the imparting method, the solvent is dried (prebaked) to form the adhesive layer. In addition, the prebaking is performed by heating using an oven, a hot plate, etc. The heating temperature and heating time in the prebaking can be appropriately selected according to the solvent used, for example, at a temperature of 60°C to 110°C for 1 minute to 3 minutes.
[0474] The thickness of the adhesive layer can be selected arbitrarily. In the present embodiment, the thickness of the adhesive layer is preferably 0.1 μm to 50 μm, and more preferably 0.5 μm to 30 μm. If the thickness of the adhesive layer is 0.1 μm or more, the adhesive layer can have sufficient holding power for adhering to the adherend. In addition, if it is 50 μm or less, the adhesive layer can be fully cured by light or heat curing.
[0475] 3-2. Exposure and Development Steps of Adhesive Layer
[0476] In addition, in this process, after the adhesive layer is applied to the surface of any one or both of the support and the adherend, an exposure process and a development process for forming a pattern on the adhesive layer may also be provided. By patterning the adhesive layer, the adhesive layer can be formed only on the part that adheres to the adherend, and in the process of separating the support and the adherend (described later), poor peeling or positional displacement of the adherend can be suppressed.
[0477] Examples of light used in the exposure process include visible light, ultraviolet light, extreme ultraviolet light, electron beam, X-ray, etc. Among the light, ultraviolet light (wavelength 250nm to 400nm) is preferred. In addition, in the development process, a developer suitable for alkali development is used. Examples of the developer include aqueous solutions of sodium carbonate, potassium carbonate, potassium hydroxide, diethanolamine, tetramethylammonium hydroxide, etc. These developers can be appropriately selected according to the characteristics of the resin layer, and surfactants can be added as needed. The development temperature is preferably 20°C to 35°C, and a commercially available developer or ultrasonic cleaning machine can be used to accurately form a fine image. In addition, water washing is usually performed after alkali development. As a development treatment method, a spray development method, a spray development method, an immersion (dip) development method, a puddle (puddle) development method, etc. can be applied.
[0478] 3-3. Step of bonding the support and the adherend
[0479] The step of bonding the support and the adherend is a step of bonding the support and the adherend via the adhesive layer.
[0480] As a method for bonding the support and the adherend, for example, there is a method of contacting the adherend (adhesive is applied to the surface in contact with the adhesive layer) with the surface of the adhesive layer formed on the surface of the support, and pressurizing while heating. In addition, regarding the bonding conditions between the support and the adherend, the temperature during pressurization is preferably above room temperature and below 200°C, more preferably 30°C to 150°C. The pressure during bonding is preferably 0.01MPa to 20MPa, more preferably 0.03MPa to 15MPa. In addition, if necessary, after the pressurized hot pressing is completed, it can be thermally cured at a temperature of 120°C to 250°C. Under the conditions, the support and the adherend are bonded, whereby the adherend is more firmly fixed to the surface of the support via the adhesive layer.
[0481] In addition, in the bonding process, the support and the adherend may be bonded by photocuring. As an example of a method for photocuring the adhesive layer, there is a method of irradiating light using a high-pressure mercury lamp. In addition, regarding the bonding conditions between the support and the adherend, the wavelength of the irradiated light is preferably 200nm to 500nm. The exposure amount of the irradiated light is preferably 25mJ / cm 2 ~3000mJ / cm 2 , more preferably 50 mJ / cm 2 ~2000mJ / cm 2 .
[0482] In this manner, the laminated body of the present embodiment is formed.
[0483] In addition, the support and the adherend of the laminate can be separated by irradiating the adhesive layer with a laser beam having a wavelength of 10 nm to 400 nm, which will be described later, from the support side.
[0484] 3-4. Step of providing a resist layer
[0485] The resist layer can be applied by a known method. Examples of methods for applying the resist layer include solution dipping, spin coating, inkjet, spraying, screen printing, curtain coating, and methods using a roll coater, a knife back coater, a slit coater, or a spinner. In addition, when a dry film resist is used, it can also be applied by laminating a dry film.
[0486] The imparting of the resist layer may be performed before i) the step of forming the adhesive layer, before ii) the step of bonding the support and the adherend, or after ii) the step of bonding the support and the adherend. In the case where the resist layer is thermosetting, it is preferred to impart the resist layer after the step of heat-treating the adhesive layer. By imparting the resist layer after the step of heat-treating the adhesive layer, the developability of the resist layer in the development step described later can be improved.
[0487] 4. Method for manufacturing a laminate comprising a patterned material layer
[0488] A method for manufacturing a stacked body including a patterned material layer (hereinafter also referred to as a "patterned material") includes: a) a preparation step of preparing a stacked body including an unexposed resist layer; b) an exposure step of irradiating a portion of the resist layer with radiation through a photomask; c) a development step of developing the resist layer irradiated with radiation to remove the exposed portion or the unexposed portion of the resist layer; and d) a stripping step of stripping the resist layer using an alkaline stripping solution.
[0489] In addition, in the preparation step a), a laminated body provided with an adhesive layer may be prepared, or an adhesive layer may be provided after the steps b) to d). From the viewpoint of improving the transport stability of the substrate in the exposure step b), the development step c), and the peeling step d), it is preferred to prepare a laminated body provided with an adhesive layer in the preparation step a).
[0490] The patterned material refers to a material in a material layer, especially a material whose material layer is patterned. For example, a material layer is formed before any of the steps a) to d), and the material layer is patterned by an etching process or a stripping process to obtain a patterned material.
[0491] For example, when the material layer is patterned by an etching process, the material layer is preferably formed before a) the preparation step. Also, when the material layer is patterned by a lift-off process, the material layer is preferably formed before d) the lift-off step.
[0492] The material layer can be provided by a known method, and examples of the material layer providing method include vapor deposition, sputtering, molecular lamination, coating, inkjet, printing, and the like.
[0493] In the case where the material layer is patterned by an etching process, the etching process can use a known method. Examples of etching processes include: plasma etching, ion etching, reactive ion etching, sputtering etching, etc. In addition, dry etching can use a known device. Examples of gases that can be used in dry etching include: fluorine-based gases such as CHF3, CF4, C2F6, C3F8, SF6, chlorine-based gases such as Cl2, BCl3, oxygen-based gases such as O2, O3, H2, NH3, CO, CO2, CH4, C2H2, C2H4, C2H6, C3H4, C3H6, C3H8, HF, HI, HBr, HCl, NO, NH3, BCl3, reducing gases, He, N2, Ar, etc., inert gases, etc. These gases can be used in combination.
[0494] 4-1. Preparation step of preparing a laminate including an unexposed resist layer
[0495] The step of preparing a laminated body including an unexposed resist layer is a step of obtaining a laminated body including a resist layer by the above-mentioned method, or preparing a laminated body to which an unexposed resist layer has been provided.
[0496] 4-2. Exposure step of irradiating a portion of the resist layer with radiation through a photomask
[0497] The exposure step is a step of irradiating a portion of the resist layer with radiation through a photomask to cause the portion of the resist layer to undergo a photoreaction.
[0498] The photomask may use a known photomask. Examples of photomasks include multi-grayscale masks such as halftone masks and gray-tone masks. In the gray-tone mask, a light-shielding portion and a diffraction grating are formed on a light-transmitting substrate. In the diffraction grating, the intervals between light-transmitting areas such as slits, dots, and grids are intervals below the resolution limit of the light used in exposure, and the transmittance of light is controlled by the structure. In the halftone mask, a light-shielding portion and a semi-transmitting portion are formed on a light-transmitting substrate. The transmittance of light used in exposure is controlled by the semi-transmitting portion.
[0499] Examples of the radiation to be irradiated include visible light, ultraviolet light, far ultraviolet light, electron beams, and X-rays. Among the radiation, ultraviolet light is preferred. In addition, the device for irradiating radiation can use a known exposure device (ultra-high pressure mercury lamp, high pressure mercury lamp, metal halide lamp, far ultraviolet lamp, etc.). In addition, the wavelength of the radiation to be irradiated is preferably 250nm to 400nm. The exposure amount of the radiation is preferably 25mJ / cm 2 ~3000mJ / cm 2 , more preferably 50 mJ / cm 2 ~2000mJ / cm 2 .
[0500] 4-3. Developing step of developing the resist layer to remove the exposed portion or the unexposed portion
[0501] The development step is a step of developing the resist layer irradiated with radiation. When the resist layer is positive, the exposed portion is removed, and when the resist layer is negative, the unexposed portion is removed. The development method can be appropriately selected from known methods according to the type of the resist layer.
[0502] Examples of the method for developing the resist layer include shower development, spray development, dip development, and puddle development. The development method can be performed using a commercially available developer or ultrasonic cleaner.
[0503] In addition, in the case of alkali development, examples of alkali developers include aqueous solutions of alkalis (basic compounds) such as sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate, lithium carbonate, sodium silicate, sodium metasilicate, ammonia, ethylamine, n-propylamine, diethylamine, diethylaminoethanol, di-n-propylamine, triethylamine, methyldiethylamine, dimethylethanolamine, triethanolamine, tetramethylammonium hydroxide, tetraethylammonium hydroxide, pyrrole, piperidine, 1,8-diazabicyclo〔5.4.0〕-7-undecene, 1,5-diazabicyclo〔4.3.0〕-5-nonane, etc. The alkali development method can be appropriately selected from known methods according to the type of etching resist.
[0504] 4-4. Stripping step of stripping the resist layer using an alkaline stripping solution
[0505] The stripping solution is a step of stripping the resist layer using an alkaline stripping solution to remove it from the laminate.
[0506] In the stripping process, as long as at least the resist layer can be stripped. For example, when the resist layer is stripped by an etching process, the resist layer is preferably stripped from the material layer. In addition, when the adherend is patterned or when the resist layer is removed by a stripping process, the resist layer is preferably stripped from the adherend.
[0507] The alkaline stripping solution can use a known stripping solution. As such a stripping solution, for example, an alkaline stripping solution containing sodium hydroxide can be used. When an alkaline developer is used for development, the alkaline stripping solution is more alkaline than the alkaline developer used in the development process, and the resist layer that is not removed in the developer can be stripped. In addition, when an aqueous sodium hydroxide solution is used in the alkaline stripping solution, it is preferred to use a 5% to 20% by mass solution. The temperature of the alkaline stripping solution in the stripping process is preferably 40°C to 80°C. In addition, the contact time of the alkaline stripping solution is preferably 5 minutes to 60 minutes. By setting the concentration, temperature, and contact time of the alkaline stripping solution to the above range, the resist layer can be stripped well.
[0508] In this manner, a laminate including the patterning material of this embodiment is formed.
[0509] In addition, the support and the adherend of the laminate can be separated by irradiating the adhesive layer with a laser beam having a wavelength of 10 nm to 400 nm, which will be described later, from the support side.
[0510] 5. Method for processing laminated body
[0511] The method for treating a laminated body of the present embodiment comprises: (1) a process of preparing the laminated body; and (2) a process of irradiating the laminated body with light to separate the support body from the adherend. Each process is described below. In addition, the process (1) and the process (2) can be performed consecutively, or the process (2) can be performed after a certain period of time after the process (1).
[0512] The laminate can be used to transport multiple adherends held by a support. As described above, the adherend can be a single layer or a multilayer with more than two layers. In addition, in the laminate, a resist layer or a material layer can be arranged on the opposite side of the adherend's surface in contact with the adhesive layer, and the adherend, the resist layer, and the material layer can be patterned layers or unpatterned layers, respectively.
[0513] 5-1. Step of preparing a laminate
[0514] The step of preparing a laminated body is a step of forming a laminated body as described above, or preparing an already formed laminated body.
[0515] 5-2. Step of separating the support and the adherend
[0516] The step of separating the support and the adherend is a step of separating the support and the adherend by irradiating the adhesive layer with light.
[0517] The irradiated light is not particularly limited as long as it can separate the support from the adherend. In the present embodiment, the light is preferably ultraviolet light, and the wavelength of the ultraviolet light is more preferably 10nm to 400nm, and more preferably 100nm to 400nm. If the wavelength of the ultraviolet light is greater than 10nm, the polymer as a component of the adhesive layer will deteriorate by absorbing light, thereby reducing the strength and adhesion, so that the support and the adherend can be easily separated. In addition, if the wavelength is less than 400nm, the adhesive layer of the processed part absorbs light, so that the residue of the cured film can be suppressed.
[0518] Examples of the ultraviolet light source include a low-pressure mercury lamp, a high-pressure mercury lamp, an ultrahigh-pressure mercury lamp, a metal halide lamp, a far-ultraviolet lamp, and a laser. Among the light sources, a laser is preferred.
[0519] Examples of the laser include solid lasers, liquid lasers, and gas lasers. In addition, examples of the solid laser include semiconductor excitation lasers, etc. Examples of liquid lasers include pigment lasers, etc. Examples of gas lasers include excimer lasers, etc. Among the lasers, semiconductor excitation lasers are preferred.
[0520] Examples of the semiconductor excitation laser include: Nd: yttrium aluminum garnet (YAG) laser, Nd: yttrium lithium fluoride (YLF) laser, Nd: glass laser, Nd: YVO4 laser, Yb: YAG laser, Yb-doped fiber laser, Er: YAG laser, Tm: YAG laser, etc. Examples of excimer laser include: KrF laser, XeCl laser, ArF laser, F2 laser, etc. Among the lasers, Nd: YAG laser is preferred.
[0521] The output power and the accumulated light quantity of the light irradiated to the adhesive layer vary depending on the type of light source, etc. When the irradiated light is laser, the output power can be 0.1 mW to 200 W. In addition, the accumulated light quantity is preferably 1 mJ / cm 2 ~50J / cm 2 If the cumulative light intensity is 0.1mJ / cm 2 If the ablation temperature is 50 J / cm 2 Next, the ablation speed can be appropriately controlled to perform appropriate processing.
[0522] As a method of irradiating the adhesive layer with light (laser), it is preferable to irradiate the entire surface of the adhesive layer with laser light from the support side. The method of irradiating with laser light is not particularly limited and can be performed by a known method.
[0523] In the laminate, the support and the adherend can be separated by irradiating the adhesive layer with light (laser).
[0524] The method for treating a laminated body according to the present embodiment may include a step of processing the prepared laminated body before the step of separating the support body from the adherend.
[0525] Methods for processing the laminate include thinning of the adherend by dicing, back grinding, photolithography, lamination of semiconductor chips, mounting of various components, resin sealing, and the like.
[0526] In addition, the method for processing the stacked body of the present embodiment may include a step of moving the processed stacked body from one device to another device. As a method for moving the stacked body, a robot arm or the like is included.
[0527] In this manner, the laminated body of the present embodiment is processed.
[0528] [Example]
[0529] Hereinafter, the embodiment of the present invention will be described in detail based on Examples and Comparative Examples, but the present invention is not limited thereto.
[0530] First, the synthesis examples of the unsaturated group-containing polymerizable resin as the component (A) will be described. However, unless otherwise specified, the evaluation of the resins in these synthesis examples was performed as described below.
[0531] In addition, for various measuring equipment, when the same model is used, the name of the equipment manufacturer is omitted from the second place. In addition, in the examples, all glass substrates used in the preparation of the substrate with a hardened film for measurement are subjected to the same treatment and used. In addition, for the content of each component, when the first decimal place is 0, the expression after the decimal point is sometimes omitted.
[0532] [Solid content concentration]
[0533] 1 g of the resin solution obtained in the synthesis example was impregnated in a glass filter [weight: W0 (g)] and weighed [W1 (g)]. The weight after heating at 160° C. for 2 hours [W2 (g)] was determined using the following formula.
[0534] Solid content concentration (weight %) = 100 × (W2-W0) / (W1-W0)
[0535] [Acid value]
[0536] The resin solution was dissolved in dioxane, and titrated with a 1 / 10 N-KOH aqueous solution using a potentiometric titrator "COM-1600" (manufactured by Hiranuma Sangyo Co., Ltd.) to obtain the molecular weight.
[0537] [Molecular weight]
[0538] The weight average molecular weight (Mw) was determined using a gel permeation chromatograph (GPC) "HLC-8220GPC" (manufactured by Tosoh Corporation, solvent: tetrahydrofuran, columns: TSKgelSuper H-2000 (2 columns) + TSKgelSuper H-3000 (1 column) + TSKgelSuper H-4000 (1 column) + TSKgelSuper H-5000 (1 column) (manufactured by Tosoh Corporation), temperature: 40°C, rate: 0.6 ml / min) and the weight average molecular weight (Mw) was determined as a standard polystyrene (manufactured by Tosoh Corporation, PS-oligomer set) conversion value.
[0539] [Absorbance of component (A) at 260 nm to 400 nm]
[0540] The absorbance can be set to a value obtained by measuring the absorbance of a 0.001 wt % PGMEA solution in a quartz cell with an optical path length of 1 cm using an ultraviolet-visible-infrared spectrophotometer "UH4150" (manufactured by Hitachi High-Tech Sciences, Inc.).
[0541] [Absorbance of component (B) at a wavelength of 266 nm]
[0542] The absorbance can be set to a value obtained by measuring the absorbance of a 0.001 wt % acetonitrile solution in a quartz cell with an optical path length of 1 cm using an ultraviolet-visible-infrared spectrophotometer "UH4150" (manufactured by Hitachi High-Tech Sciences, Inc.).
[0543] The abbreviations described in the synthesis examples are as follows.
[0544] BPFE: bisphenol fluorene epoxy resin (in the general formula (5), Ar is a benzene ring, l is 0, and the epoxy equivalent is 256 g / eq)
[0545] AA: Acrylic acid
[0546] TPP: triphenylphosphine
[0547] PGMEA: Propylene glycol monomethyl ether acetate
[0548] BPDA: 3,3',4,4'-biphenyltetracarboxylic dianhydride
[0549] THPA: 1,2,3,6-Tetrahydrophthalic anhydride
[0550] RUVA-93: 2-(2'-Hydroxy-5'-methacryloyloxyethylphenyl)-2-H-benzotriazole (manufactured by Otsuka Chemical Co., Ltd.)
[0551] MMA: Methyl Methacrylate
[0552] MA: Methacrylic acid
[0553] HEMA: 2-Hydroxyethyl Methacrylate
[0554] ADVN: 2,2'-azobis(2,4-dimethylvaleronitrile)
[0555] MOI: 2-isocyanatoethyl methacrylate
[0556] DCPMA: Dicyclopentyl methacrylate
[0557] GMA: Glycidyl Methacrylate
[0558] St:Styrene
[0559] AIBN: Azobisisobutyronitrile
[0560] TDMAMP: tris-dimethylaminomethylphenol
[0561] HQ: Hydroquinone
[0562] SA: Succinic anhydride
[0563] TEA: triethylamine
[0564] [Synthesis example 1]
[0565] BPFE (50.00 g, 0.10 mol), AA (14.07 g, 0.20 mol), TPP (0.26 g), and PGMEA (40.00 g) were placed in a 250 mL four-necked flask equipped with a reflux cooler, and stirred at 100° C. to 105° C. for 12 hours to obtain a reaction product. PGMEA (25.00 g) was then added to the reaction product to adjust the solid content to 50.0% by mass.
[0566] Next, BPDA (14.37 g, 0.05 mol) and THPA (7.43 g, 0.05 mol) were added to the obtained reaction product, and stirred at 115° C. to 120° C. for 6 hours to obtain an unsaturated group-containing alkali-soluble resin (A)-1. The obtained resin solution had a solid content concentration of 57.0% by mass, an acid value (solid content conversion) of 96 mgKOH / g, and a Mw obtained by GPC analysis of 3600. In addition, the maximum value of the absorbance at 260 nm to 400 nm was 0.22 (275 nm).
[0567] [Synthesis example 2]
[0568] BPFE (50.00 g, 0.10 mol), AA (14.07 g, 0.20 mol), TPP (0.26 g), and PGMEA (40.00 g) were placed in a 250 mL four-necked flask equipped with a reflux cooler, and stirred at 100° C. to 105° C. for 12 hours to obtain a reaction product. PGMEA (25.00 g) was then added to the reaction product to adjust the solid content to 50.0% by mass.
[0569] Next, BPDA (10.06 g, 0.03 mol) and THPA (11.89 g, 0.08 mol) were added to the obtained reaction product, and stirred at 115° C. to 120° C. for 6 hours to obtain an unsaturated group-containing alkali-soluble resin (A)-2. The obtained resin solution had a solid content concentration of 57.0% by mass, an acid value (solid content conversion) of 98 mgKOH / g, and a Mw obtained by GPC analysis of 2300. In addition, the maximum value of the absorbance at 260 nm to 400 nm was 0.20 (275 nm).
[0570] [Synthesis example 3]
[0571] BPFE (50.00 g, 0.10 mol), AA (14.07 g, 0.20 mol), TPP (0.26 g), and PGMEA (40.00 g) were placed in a 250 mL four-necked flask equipped with a reflux cooler, and stirred at 100° C. to 105° C. for 12 hours to obtain a reaction product. PGMEA (25.00 g) was then added to the reaction product to adjust the solid content to 50.0% by mass.
[0572] Next, BPDA (19.25 g, 0.07 mol) and THPA (0.30 g, 0.002 mol) were added to the obtained reaction product, and stirred at 115° C. to 120° C. for 6 hours to obtain an unsaturated group-containing alkali-soluble resin (A)-3. The obtained resin solution had a solid content concentration of 56.3% by mass, an acid value (solid content conversion) of 97 mgKOH / g, and a Mw obtained by GPC analysis of 4700. In addition, the maximum value of the absorbance at 260 nm to 400 nm was 0.23 (275 nm).
[0573] [Synthesis Example 4]
[0574] In a reactor including a temperature regulator, a stirrer, a reflux cooler, and a nitrogen inlet pipe, PGMEA (233 parts by weight) as a solvent, RUVA-93 (59 parts by weight, 0.18 mol) as an unsaturated monomer containing a UV absorbing group, MMA (16 parts by weight, 0.16 mol) and MA (9.0 parts by weight, 0.10 mol), and HEMA (15 parts by weight, 0.12 mol) as other unsaturated monomers were added, heated to 80°C, and replaced with nitrogen. ADVN (2 parts by weight) as a polymerization initiator was added and reacted for 1 hour. Thereafter, ADVN (0.5 parts by weight) was added, heated to 90°C, and aged for 3 hours to synthesize a UV absorbing copolymer. In addition, the molar absorption coefficient of RUVA-93 at a wavelength of 355 nm is 17000 L / (mol·cm). The molar absorption coefficient can be calculated by measuring the absorbance of a 0.001 wt % acetonitrile solution in a quartz cell with an optical path length of 1 cm using an ultraviolet-visible-infrared spectrophotometer "UH4150" (manufactured by Hitachi High-Tech Sciences, Ltd.) and dividing the result by the molar concentration.
[0575] MOI (18 parts by weight, 0.12 mol), a tin compound (0.01 parts by weight) as a catalyst, and p-methoxyphenol (0.04 parts by weight) as a polymerization inhibitor were added thereto, and the ultraviolet absorbing copolymer was subjected to MOI addition reaction at 60°C for about 6 hours. The end point of the reaction was confirmed by the disappearance of the isocyanate peak according to Fourier transform infrared spectroscopy (FT-IR). After the reaction was completed, PGMEA was added thereto and adjusted to a solid content of 30.0% by weight to obtain an alkali-soluble resin (A)-4 containing an unsaturated group. The acid value (solid content conversion) of the obtained resin solution was 55 mgKOH / g, and the Mw obtained by GPC analysis was 30,000. In addition, the maximum value of the absorbance at 260nm to 400nm was 0.25 (334nm).
[0576] [Synthesis Example 5]
[0577] PGMEA (300 g) was placed in a 1L four-necked flask equipped with a reflux cooler, and the flask system was purged with nitrogen and then heated to 120° C. A mixture of AIBN (10 g) dissolved in a monomer mixture (DCPMA (77.1 g, 0.35 mol), GMA (49.8 g, 0.35 mol), St (31.2 g, 0.30 mol)) was added dropwise from a dropping funnel to the flask over 2 hours, and the mixture was further stirred at 120° C. for 2 hours to obtain a copolymer solution.
[0578] Next, after replacing the inside of the flask system with air, AA (24.0 g, 95% of glycidyl groups), TDMAMP (0.8 g) and HQ (0.15 g) were added to the obtained copolymer solution, and stirred at 120°C for 6 hours to obtain a copolymer solution containing polymerizable unsaturated groups. SA (30.0 g, 90% of the added molar number of AA) and TEA (0.5 g) were added to the obtained copolymer solution containing polymerizable unsaturated groups, and reacted at 120°C for 4 hours to obtain an alkali-soluble resin (A)-5 containing unsaturated groups. The solid content concentration of the resin solution was 46.0% by mass, the acid value (solid content conversion) was 76 mgKOH / g, and the Mw obtained by GPC analysis was 5300. In addition, the maximum value of the absorbance at 260nm to 400nm was 0.05 (270nm).
[0579] Adhesive layer-forming compositions were prepared in the amounts (unit: mass %) described in Tables 1 and 2. The components used in Tables 1 and 2 are as follows.
[0580] (Alkali-soluble resin containing unsaturated groups)
[0581] (A)-1: Resin solution obtained in Synthesis Example 1 (solid content concentration: 57.0 mass %)
[0582] (A)-2: Resin solution obtained in Synthesis Example 2 (solid content concentration: 57.0 mass %)
[0583] (A)-3: Resin solution obtained in Synthesis Example 3 (solid content concentration: 56.3% by mass)
[0584] (A)-4: Resin solution obtained in Synthesis Example 4 (solid content concentration: 30.0 mass %)
[0585] (A)-5: Resin solution obtained in Synthesis Example 5 (solid content concentration: 46.0 mass %)
[0586] (Epoxides)
[0587] (B)-1: Biphenyl type epoxy resin (jER YX4000, manufactured by Mitsubishi Chemical Corporation, "jER" is a registered trademark of the company, epoxy equivalent: 190 g / eq)
[0588] (B)-2: Bisphenol A type epoxy resin (jER 828, manufactured by Mitsubishi Chemical Co., Ltd., "jER" is a registered trademark of the company, epoxy equivalent: 185 g / eq)
[0589] (B)-3: Bisphenol fluorene diglycidyl ether (epoxide equivalent: 256 g / eq)
[0590] (B)-4: 1,2-epoxy-4-(2-oxacyclopropyl)cyclohexane adduct of 2,2-bis(hydroxymethyl)-1-butanol (EHPE3150, manufactured by Daicel Corporation, epoxy equivalent: 180 g / eq)
[0591] (B)-5: trimethylolpropane triglycidyl ether (Epolight 100MF, manufactured by Kyoeisha Chemical Co., Ltd., epoxy equivalent: 140 g / eq)
[0592] (B)-6: Shofree BATG (manufactured by Resonac Co., Ltd., "Shofree" is a registered trademark of the company, epoxy equivalent weight is 120 g / eq)
[0593] (Polymerizable compound)
[0594] (C)-1: A mixture of dipentaerythritol pentaacrylate and dipentaerythritol hexaacrylate (DPHA, manufactured by Nippon Kayaku Co., Ltd.)
[0595] (C)-2: ethylene oxide 6 mol adduct of trimethylolpropane triacrylate (Aronix M-360, manufactured by Toagosei Co., Ltd.)
[0596] (Solvent)
[0597] (D)-1: Propylene glycol monomethyl ether acetate (PGMEA)
[0598] (D)-2: Cyclohexanone (ANON)
[0599] [Table 1]
[0600]
[0601]
[0602] [evaluate]
[0603] The compositions for forming an adhesive layer described in Tables 1 and 2 were evaluated as follows.
[0604] [Laser processability (peelability) evaluation]
[0605] (Preparation of a Substrate for Evaluation of Laser Processability (Removability))
[0606] The adhesive layer-forming composition shown in Table 1 and Table 2 was applied to a glass substrate "#1737" using a spin coater so that the film thickness after drying was 1.0 μm, and pre-baked at 100° C. for 5 minutes using a hot plate to prepare a coating film. Next, a hot air dryer was used to perform full curing (post-baking) at 230° C. for 30 minutes to obtain substrates with cured films of Examples 1 to 15 and Comparative Examples 1 to 5.
[0607] (Evaluation method)
[0608] The cured film after the main curing (post-baking) was irradiated with laser light (laser wavelength: 266 nm) using a flash lamp to excite the Nd:YAG Q-SW laser oscillator "Callisto" (manufactured by V-Technology Co., Ltd.). 2 ~550mJ / cm 2 The hardened film was processed (removed) with laser energy of , and the amount of film reduction in the laser irradiated part was measured using a non-contact three-dimensional optical interference microscope "WYKO Contour-GT" (manufactured by Bruker Japan). The evaluation was performed based on the laser irradiation amount used to reduce the film amount to 0.1 μm. In addition, △ or above was considered qualified.
[0609] (Evaluation Criteria)
[0610] ◎:100mJ / cm 2 Below, the film reduction amount becomes 0.1μm
[0611] ○: More than 100mJ / cm 2 And 150mJ / cm 2 Below, the film reduction amount becomes 0.1μm
[0612] △: more than 150mJ / cm 2 And 200mJ / cm 2 Below, the film reduction amount becomes 0.1μm
[0613] ×: more than 200 mJ / cm 2 , the reduction of the hardened film is less than 0.1μm
[0614] (Preparation of a substrate with a cured film for evaluation of alkali resistance)
[0615] The adhesive layer-forming composition shown in Table 1 and Table 2 was applied to a glass substrate "#1737" using a spin coater so that the film thickness after heat curing was 4.0 μm, and pre-baked at 100° C. for 5 minutes using a hot plate to prepare a coating film. Next, a hot air dryer was used to perform full curing (post-baking) at 230° C. for 30 minutes to obtain substrates with cured films of Examples 1 to 15 and Comparative Examples 1 to 5.
[0616] [Alkali resistance evaluation]
[0617] (Evaluation method)
[0618] The cured film of the substrate with the cured film was immersed in an 8.7% by mass sodium hydroxide aqueous solution at 70°C for 10 minutes, then washed with pure water and dried. After that, the thickness of the cured film after the test was measured using a stylus-type step shape measuring device "P-17" (manufactured by KLA-Tencor Co., Ltd.). In addition, △ or above was considered qualified.
[0619] The residual film ratio in the alkali resistance evaluation was calculated according to the following formula, with the film thickness before the test being defined as L1 and the film thickness after the test being defined as L2.
[0620] Residual film rate (%) = L2 / L1×100
[0621] (Evaluation Criteria)
[0622] ◎: Residual film rate is more than 95%
[0623] ○: Residual film rate is more than 90%
[0624] △: The residual film rate is 80% or more and less than 90%
[0625] ×: The residual film rate is less than 80%
[0626] (Preparation of a Substrate for Evaluation of Shear Strength (Adhesion Strength))
[0627] The adhesive layer-forming composition shown in Table 1 and Table 2 was applied on a glass substrate "#1737" using a spin coater so that the film thickness after heat curing was 4.0 μm, and pre-baked at 100° C. for 5 minutes using a hot plate to prepare a dry film.
[0628] Next, a glass substrate "#1737" cut into 2 mm × 2 mm was placed on the pattern and pressed at 110°C for 1 minute while applying a pressure of 0.3 MPa. After that, a hot air dryer was used to perform formal curing (post-baking) at 230°C for 30 minutes to obtain a substrate with a cured film for the shear strength (adhesion strength) evaluation of Examples 1 to 15 and Comparative Examples 1 to 5.
[0629] (Evaluation method)
[0630] The shear strength (adhesion strength) of the 2 mm×2 mm glass substrate "#1737" bonded to the obtained substrate with a cured resin film was measured using a die shear tester (manufactured by Arktech). A score of △ or above was considered acceptable.
[0631] (Evaluation Criteria)
[0632] ◎: Shear strength (adhesion strength) is 20 MPa or more
[0633] ○: Shear strength (adhesive strength) is 18 MPa or more and less than 20 MPa
[0634] △: Shear strength (adhesion strength) is 16 MPa or more and less than 18 MPa
[0635] ×: Shear strength (adhesion strength) less than 16 MPa
[0636] The evaluation results are shown in Tables 3 and 4.
[0637]
[0638] [Reference experiment: solvent immersion evaluation]
[0639] In addition, as a reference experiment, an alkali solution immersion evaluation under milder conditions than the alkali resistance evaluation was performed. Using the substrate with the cured film of the substrate with the cured film used in the alkali resistance evaluation, the substrate of Example 1, Example 6, Example 10, Example 13, and Comparative Example 5 was immersed in a 5wt% sodium hydroxide aqueous solution at 25°C for 30 minutes, and then cleaned and dried. After that, the film thickness of the cured film after the test was measured using a stylus-type step difference shape measuring device "P-17" (manufactured by KLA-Tencor Co., Ltd.). In addition, △ or above is considered qualified.
[0640] The residual film rate in the chemical resistance evaluation was calculated according to the following formula, with the film thickness before the test being defined as L1 and the film thickness after the test being defined as L2.
[0641] Residual film rate (%) = L2 / L1×100
[0642] (Evaluation Criteria)
[0643] ○: Residual film rate is more than 90%
[0644] △: The residual film rate is 80% or more and less than 90%
[0645] ×: The residual film rate is less than 80%
[0646] Table 5 shows the evaluation results.
[0647] [Table 5]
[0648]
[0649] As is clear from Tables 3 and 4, in the adhesive layer forming composition, by setting the content of component (B) to 25% to 70% by mass relative to the mass of component (A), both laser processability (peeling properties) and alkali resistance can be achieved, and the shear strength (adhesion strength) is also at an acceptable level.
[0650] Comparison between Example 1 and Examples 7 to 11 shows that the alkali resistance is improved even when the addition amount of the component (B) is the same, because the component (B) has at least one aromatic ring or alicyclic structure in the molecule.
[0651] Comparison between Example 1 and Examples 7 to 11 shows that by setting the absorbance of the component (B) at 266 nm to 0.10 or more, the processability (peelability) of the adhesive layer by a 266 nm laser can be improved.
[0652] According to the comparison of Example 1 and Example 12 to Example 15, by setting the content of component (C) to 1% by mass to 10% by mass relative to the total mass of component (A) and component (B), the shear strength (bonding strength) can be improved while maintaining laser processability (peeling properties) and alkali resistance.
[0653] In addition, according to the reference experiment, even in the comparative example, the alkali solution immersion evaluation reached the allowable level as long as the alkali treatment conditions were mild. Therefore, it can be seen that the alkali resistance evaluation of this example is a strict evaluation condition, and it can be seen that the adhesive layer of this embodiment has high alkali resistance.
[0654] [Industrial Applicability]
[0655] The present invention can provide a laminate having an adhesive that can be used in the manufacture of various products, and can provide a laminate that is suitable for a process of temporarily fixing a semiconductor wafer or the like to a support for processing.
Claims
1. A composition for forming an adhesive layer, wherein in a laminate including an adhesive layer between a light-transmitting support and an adherend, The support and the adherend can be separated from the laminate by irradiating light from the support side, and the adhesive layer-forming composition includes: (A) an alkali-soluble resin containing an unsaturated group; (B) an epoxy compound having at least two epoxy groups; and (D) a solvent, The content of the epoxy compound (B) is 25% by mass to 70% by mass based on the total mass of the unsaturated group-containing alkali-soluble resin (A).
2. The adhesive layer-forming composition according to claim 1, wherein The (B) epoxy compound has an aromatic ring and / or an alicyclic structure.
3. The adhesive layer-forming composition according to claim 1, wherein The epoxy compound (B) The absorbance of light at a wavelength of 266 nm after measuring the absorbance of a 0.001 wt % acetonitrile solution in a quartz cell with an optical path length of 1 cm using an ultraviolet-visible-infrared spectrophotometer is 0.10 or more.
4. The adhesive layer-forming composition according to claim 1, wherein The weight average molecular weight of the unsaturated group-containing alkali-soluble resin (A) is 1,000 to 40,000, The acid value is 20 mgKOH / g to 200 mgKOH / g.
5. The adhesive layer-forming composition according to claim 1, comprising (C) a polymerizable compound having at least one ethylenically unsaturated bond, The content of the (C) polymerizable compound is 1% by mass to 10% by mass based on the total mass of the (A) unsaturated group-containing alkali-soluble resin and the (B) epoxy compound.
6. A laminate comprising: Support body; adherend; and The adhesive layer is disposed between the support and the adherend and includes a coating film or a cured film of the adhesive layer-forming composition according to any one of claims 1 to 5.
7. The laminate according to claim 6, comprising a resist layer, the resist layer being arranged on a surface of the adherend opposite to a surface on which the adhesive layer is arranged, The resist layer is arranged in contact with an adherend, or is arranged so that a material layer is sandwiched between the resist layer and the adherend. 8 . The laminate according to claim 6 , comprising a material layer which is arranged on a surface of the adherend opposite to a surface on which the adhesive layer is arranged and is patterned.
9. A method for manufacturing a laminate, comprising: A step of forming an adhesive layer on the surface of one or both of a support and an adherend using the adhesive layer-forming composition according to any one of claims 1 to 5; and a step of bonding the support and the adherend together via the formed adhesive layer.
10. The method for producing a laminate according to claim 9, comprising the step of providing a resist layer on the adherend, The resist layer is arranged on a surface opposite to a surface on which the adhesive layer is arranged.
11. A method for treating a laminate, comprising: A step of preparing a laminate according to any one of claims 6 to 8; and The step of irradiating the adhesive layer with light to separate the support and the adherend, in the method for treating the laminate, The support transmits light having a wavelength of 10 nm to 400 nm.
12. A method for manufacturing a laminate, wherein the laminate comprises a patterned material layer, the method comprising: A step of preparing a laminated body, the laminated body comprising: Support body; Adhesive body; an adhesive layer disposed between the support and the adherend and comprising a coating film or a cured film of the adhesive layer-forming composition according to any one of claims 1 to 5; and A resist layer is disposed on the surface of the adherend opposite to the surface on which the adhesive layer is disposed and is not exposed; an exposure step of irradiating a portion of the resist layer with radiation through a photomask; A developing step of developing the resist layer irradiated with radiation to remove the exposed portion or the unexposed portion of the resist layer; as well as In the stripping step, the resist layer is stripped using an alkaline stripping solution.
Citation Information
Patent Citations
Resin composite, solder resist resin composite, and hardened materials thereof
JP1992355450A
Alkali development unsaturated resin component and highly sensitive negative type pattern formation material using the same
JP1997325494A
Ultraviolet-curable resin and coating agent obtained using the same
JP2004182924A
Microcapsule for electrophoresis display
JP2007286123A
Laminates for optics
JP2007331359A